Comparative risk factors among pancreatic adenocarcinoma patients vs. neuroendocrine and other pancreatic cancer patients - Daniel C. Beachler; Lauren E. Parlett; Jessica L. Petrick; Stephan Lanes; John Barron; David Debono; Michael J. Fisch (Cancer Causes & Control, 2026)

Flight demonstration of a CubeSat Sporadic-E detector - Bruce A. Fritz; Kenneth F. Dymond; Ellen J. Wagner; Andrew C. Nicholas; Scott A. Budzien; Andrew W. Stephan (Advances in Space Research, 2026)

Environmental uncertainty affects movement and space-use in sheep - Sarah T. Bartsch; William H. E. J. van Wettere; Simon C. Griffith; Stephan T. Leu (Behavioral Ecology and Sociobiology, 2026)
Animals regularly experience periods of food uncertainty due to seasonal changes and environmental variability. Further, the changing climate is leading to more variable weather patterns, which alter environmental conditions, and can result in resource distributions being less predictable in space and time. How animals respond to uncertain conditions, and in particular a changing distribution of food resources, remains largely unclear and is an important question in the field of movement and animal ecology. We used an experimental approach to study how Merino sheep ( Ovis aries ) respond to different levels of food location uncertainty in a drought-impacted region of the Australian arid zone. Sheep were unfamiliar with the experimental food locations at the start and progressively decreased their uncertainty (i.e., increased their environmental knowledge) when discovering an increasing number of foraging patches. We tracked 50 sheep with GPS collars (1 location every 15 s) and deduced their movement and space use behaviour. When food uncertainty decreased, individuals moved more directionally (greater step length, smaller turn angles) and moved greater distances per day. They also had larger daily ranges. Displacement (distance between first and last location of the day) increased once and otherwise remained similar across levels of uncertainty. Our study demonstrates how an arid zone ungulate, in a large 600 ha enclosed paddock, adjusted its movement and space use behaviour as it gained environmental information on food distribution. Our study provides important insights into how animals cope with variable environments in order to forage efficiently during periods of uncertainty. Significance statement Food distributions are often unpredictable over time, with climate change exacerbating variability. Understanding how animals respond to periods of environmental uncertainty is crucial to predict animal movement in space and time. We used an experimental approach and investigated how different levels of food location uncertainty affected the movement and space-use behaviour in sheep freely moving in a large 600 ha paddock. We used the number of discovered experimental food patches as a proxy for environmental knowledge (inverse of uncertainty). Movement was faster and more directional, and daily range size increased as food uncertainty decreased and sheep gained knowledge about the food locations. Our study demonstrates how an arid zone ungulate adjusted its movement and space use behaviour as it gained environmental information about food patch distributions.

Oxygen dynamics in eastern tropical South American estuaries: effects of human activities and climate variability - Ester M. Dos Santos; Mário Barletta; Francisco J. A. Cysneiros; Stephan Carty; Julia C. M. Pereira; Eloisa R. V. Reis; Anderson L. R. Paiva (Frontiers in Marine Science, 2026)
Dissolved oxygen (DO) dynamics in estuarine ecosystems are shaped by both anthropogenic activities and climate variability, which jointly influence oxygen concentrations and overall ecosystem health. This study examined temporal and spatial variations in DO across three coastal sectors in Eastern South America. DO levels were classified as hypoxia (<2.0mgL-¹),intermediate(2.0–4.0mgL¹), and optimum (>4.0mgL-¹).Hypoxia was associated with elevated BOD, ammonia, and phosphorus, particularly in the Metropolitan sector, where low DO persisted year-round. In this sector, hypoxia rates exceeded 40% during multiple years (2005–2008 and 2010–2013). The North (2005) and South sectors (2005 and 2007) also experienced hypoxia, mainly during dry periods, with DO levels below 2.0 mg L⁻¹ in specific years. Climate variability, especially El Niño–Southern Oscillation (ENSO) events, intensified hypoxia during droughts. In the Metropolitan sector, consecutive El Niño and La Niña years (2006 and 2008) resulted in a 40% hypoxia rate. The Northern sector exhibited 38% hypoxia during the 2005 El Niño event. Increased water movement under favourable oxygen conditions enhanced oxygenation. Salinity, temperature,pH, and spatial heterogeneity were also significant determinants. These findings indicate that oxygen dynamics are regulated by both persistent pollution and interannual climate variability. The results highlight the need for integrated management strategies that address anthropogenic impacts and the rising frequency of climate extremes.

Gas chromatography analysis of fatty acid esters and free fatty acids for the evaluation of lipase performance in textile treatment and washing - Luís C. de Sousa; Nazanin Ansari; Roland Lottenbach; Rainer Rösch; Jan Modregger; Simona Capone; Karl-Erich Jaeger; Rebecka Molitor; Stephan Thies; Paula Vidal; Manuel Ferrer; Carla C.C.R. de Carvalho (Bioresource Technology Reports, 2026)

Why is Energetic Particle Precipitation Important for Climate Research and Seasonal Forecasting? - Hilde Nesse; Timo Asikainen; Margot Decotte; Bernd Funke; V. Lynn Harvey; Jia Jia; Hanli Liu; Huixin Liu; Ville Maliniemi; Noora Partamies; Josephine A. Salice; Antti Salminen; et al. (Surveys in Geophysics, 2026)

Thermal stress has greater impact on the zebrafish skin microbiota than host genotype - Daniel E. Sadler; Phillip C. Watts; Stephan N. van Dijk; Silva Uusi-Heikkilä (Journal of Thermal Biology, 2026)

Pathogens in the garden dormouse Eliomys quercinus - Sarah P. Stubbe; Eva Marie Kramer; Sven Büchner; Christine Jelinek; Calvin Mehl; René Ryll; Elisa Heuser; Dania Richter; Donata Hoffmann; Emilija Vasiliūnaitė; Christopher B. Buck; Indrė Kučinskaitė-Kodzė; et al. (European Journal of Wildlife Research, 2026)
Wild rodents are important reservoirs and vectors of various pathogens, and play a crucial role in the spread of zoonotic pathogens. The garden dormouse ( Eliomys quercinus ), an arboreal nocturnal rodent species native to Europe, has declined throughout much of its natural range in recent decades. The reason for this ongoing decline is not yet fully understood, but infectious diseases may play a role. This study aimed to review the diversity of pathogens associated with the garden dormouse. For this purpose, a comprehensive review of the existing literature on garden dormouse-associated viruses, bacteria and protozoa was conducted. In parallel, we analysed samples from 294 garden dormice, that were found dead in Germany, for rodent-associated and zoonotic pathogens. The scientific literature currently, comprising 53 references, covers 73 years and primarily addresses Borrelia spp. and Eimeria myoxi . In the literature, a total of eight pathogens have been detected in garden dormice. In our own investigations, we were able to detect four different pathogens as well as antibodies against hepatitis E virus. The most prevalent pathogen found in our study was Staphylococcus aureus (29%, n = 58). Borrelia spielmanii and B. afzelii were found in 5.6% of garden dormice ( n = 143) and 22% of the ticks attached to garden dormice ( n = 32). This study reports the first documentation of Leptospira spp. in garden dormice, with L . borgpetersenii , serogroup Sejroe, sequence type 197 detected in 2 of 176 animals. Beside these zoonotic pathogens metagenomic sequencing of selected samples revealed representatives of multiple DNA-virus families, including Parvoviridae and Polyomaviridae , most likely without zoonotic potential. There is currently no evidence, either from the literature or from our own investigations, that pathogens play a significant role in the decline of the garden dormouse in Germany.

Estimation of Sea State Parameters from Measured Ship Motions with a Neural Network Trained on Experimentally Validated Model Simulations - Jason M. Dahl; Annette R. Grilli; Stephanie C. Steele; Stephan T. Grilli (Journal of Marine Science and Engineering, 2026)
The use of ships and boats as sea-state (SS) measurement platforms has the potential to expand ocean observations while providing actionable information for real-time operational decision-making at sea. Within the framework of the Wave Buoy Analogy (WBA), this work develops an inverse approach in which efficient simulations of wave-induced motions of an advancing vessel are used to train a neural network (NN) to predict SS parameters across a broad range of wave climates. We show that a reduced set of novel motion discriminant variables (MDVs)—computed from short time series of heave, roll, and pitch motions measured by an onboard inertial measurement unit (IMU), together with the vessel’s forward speed—provides sufficient and robust information for accurate, near-real-time SS estimation. The methodology targets small, barge-like tugboats whose operations are SS-limited and whose motions can become large and strongly nonlinear near their upper operating limits. To accurately model such responses and generate training data, an efficient nonlinear time-domain seakeeping model is developed that includes nonlinear hydrostatic and viscous damping terms and explicitly accounts for forward-speed effects. The model is experimentally validated using a scaled physical model in laboratory wave-tank tests, demonstrating the necessity of these nonlinear contributions for this class of vessels. The validated model is then used to generate large, high-fidelity datasets for NN training. When applied to independent numerically simulated motion time series, the trained NN predicts SS parameters with errors typically below 5%, with slightly larger errors for SS directionality under relatively high measurement noise. Application to experimentally measured vessel motions yields similarly small errors, confirming the robustness and practical applicability of the proposed framework. In operational settings, the trained NN can be deployed onboard a tugboat and driven by IMU measurements to provide real-time SS estimates. While results are presented for a specific vessel, the methodology is general and readily transferable to other ship geometries given appropriate hydrodynamic coefficients.

Repeat Expansions in a Chilean Cohort with Adult-Onset Cerebellar Ataxia - M. Leonor Bustamante; Marcelo Miranda; David Pellerin; Mariana Barreto; Claudia Silva; Ana C. Miranda; Benjamín Pizarro-Galleguillos; Octavio Azaldegui; Valentina Besa; Francisca Canals; María Eugenia Contreras; Marie-Josée Dicaire; et al. (The Cerebellum, 2025)

Challenges and Gaps in Understanding and Monitoring Low-Latitude F-region Plasma Irregularities - Astrid Maute; Tibor Durgonics; Joe Huba; Rayan Imam; Hanli Liu; Garima Malhotra; John Retterer; Claudia C. Stephan; Claudia Stolle; Endawoke Yizengaw (Surveys in Geophysics, 2025)

Recommendations for improving risk awareness, managing impacts, and delivering effective action in managing tree pests and pathogens in urban environments - Susanne Raum; C. Matilda Collins; Julie Urquhart; Monika Egerer; Stephan Pauleit (Urban Forestry & Urban Greening, 2025)

Stratospheric Gravity Waves Impact on Infrasound Transmission Losses Across the International Monitoring System - C. Listowski; C. C. Stephan; A. Le Pichon; A. Hauchecorne; Y.-H. Kim; U. Achatz; G. Bölöni (Pure and Applied Geophysics, 2025)
The international monitoring system (IMS) has been put in place to monitor compliance with the comprehensive nuclear-test-ban treaty (CTBT). Its infrasound component, dedicated to the monitoring of atmospheric events, gives also room to civil applications (e.g. monitoring of volcanic eruptions, meteorites, severe weather). Infrasound detection capabilities are largely determined by the state of the middle atmosphere. This requires an accurate knowledge of the atmospheric processes at play. More particularly internal gravity waves (GW) pose a challenge to atmospheric modelling because of unresolved processes. Using high-resolution simulation outputs over winter 2020 (20 January–1 March) we present a method to assess the impact of GW on infrasound surface transmission losses across the IMS. We validate the method by comparing simulated GW perturbations to GW lidar observations at Observatoire de Haute-Provence in France, and satellite-based GW energy estimations globally. We perform propagation simulations using atmospheric specifications where GW are filtered out and kept in, respectively. We demonstrate that the largest impact of GW across the IMS is not where GW activity is the largest, but rather where GW activity combines with infrasound waveguides not firmly set in a given direction. In northern winter, the largest variations of transmission losses at 1 Hz due to GW occur in the southern (summer) hemisphere in the direction of the main guide (westward propagation), with average values ranging between 10 and 25 dB in the first shadow zone. It corresponds to an average signal amplification of at least a factor 5 to 15, while this amplification is around 2 to 5 for the main guide in the northern winter hemisphere (eastward propagation).

Fusarium sp. Strain K-23 Alleviates Salt Stress in Arabidopsis thaliana Through its Root Hair Growth-Promoting Effect - Francis C. Onejeme; Adrián González Ortega-Villaizán; Estefanía Rodríguez-Dobreva; Basha Topel Prieto; Manish K. Patel; Selma Guendouzi; Priya Y. N. Reddy; Leonel E. Lopez; José M. Estevez; Karaba N. Nataraja; R. Uma Shaanker; Begoña Benito; et al. (Journal of Plant Growth Regulation, 2025)
Soil salinity is a significant abiotic stress factor that impedes plant growth and crop yield, particularly in arid and semi-arid regions. Recent reports indicate that 8.7% of soils globally and 20–50% of irrigated soils across all continents are affected by salt. This phenomenon jeopardizes the food security of more than 1.5 billion people worldwide. Numerous studies have elucidated the beneficial effects of diverse microbes on plant abiotic stress tolerance. In this study, we report on an observed molecular mechanism involved in the enhanced salt tolerance of Arabidopsis plants co-cultivated with the Fusarium sp. strain K-23. Employing a combination of transcriptomics, phenomics, reverse genetics, and live cell imaging, we elucidated the intricacies of biological processes that influence root growth in the interaction between A. thaliana and the fungus. Moreover, our research corroborated the beneficial effect of the fungus under salt-stress conditions for Arabidopsis and highlighted notable differences compared to previous studies. We utilized an RNA-seq approach to identify biological processes triggered in Arabidopsis roots that interact with K-23, resulting in increased salt tolerance. These experiments necessitated a more comprehensive investigation into the fungal influence on root hair development and elucidated that induced root hair growth was a prerequisite for the enhanced salt stress tolerance conferred by the fungus. Furthermore, we demonstrate that the fungus induces the expression of the NAC transcription factor JUNGBRUNNEN 1 ( JUB1 ). Elevated expression of JUB1 leads to repression of gibberellin biosynthesis, which, in turn, contributes to sustained root hair growth under salt stress conditions, which typically suppresses root hair growth substantially.

Knock Out of miRNA-30a-5p and Reconstitution of the Actin Network Dynamics Partly Restores the Impaired Terminal Erythroid Differentiation during Blood Pharming - Jessica Thiel; Duran Sürün; Desiree C. Brändle; Madeleine Teichert; Stephan R. Künzel; Ulrike Friedrich; Andreas Dahl; Kristin Schubert; Ignacy Rzagalinski; Andrej Shevchenko; Sofia Traikov; Peter Mirtschink; et al. (Stem Cell Reviews and Reports, 2025)

Fragaria ananassa DAM4 expression correlates with vegetative growth during semi-dormancy breaking - Stephan David; Philippe Kersten; Xiren Cao; Leo F. M. Marcelis; Julian C. Verdonk (Planta, 2025)
Dormancy-Associated MADS-BOX (DAM)3 and DAM4 have been described as potential regulators of winter dormancy in cultivated strawberry ( Fragaria x ananassa Duch.). These genes are upregulated under short-day conditions and downregulated under chilling conditions. The aim of the current work is to test the hypothesis that the expression of DAM3 and DAM4 correlates negatively with vegetative growth during dormancy induction and breaking. The expression of DAM3 and DAM4 as well as plant morphology and physiology was analyzed during a period of semi-dormancy induction and breaking. Furthermore, DAM3 and DAM4 expression was compared between cultivars with different chill requirements. Lastly, the DAM1 , DAM2 , DAM3 , and DAM4 expression of concurrently growing summer and winter leaves was compared at multiple stages of dormancy breaking. DAM3 and DAM4 expression negatively correlated with leaf area and petiole length. We conclude that DAM3 and DAM4 expression patterns are consistent with that of regulators of semi-dormancy. DAM4 expression in particular correlates strongly with vegetative growth during semi-dormancy breaking. DAM3 or DAM4 expression was not found to correlate with the cultivar-specific chill requirements. Lastly, no relevant differences in DAM expression were found between summer and winter leaves.

Unraveling Predominantly Inattentive ADHD (ADHD-PI): Insights from Proteomic Analysis of the Striatum of Thyroid Hormone-Responsive Protein (THRSP)–Overexpressing Mice - Raly James Perez Custodio; Leandro Val Sayson; Ara Cho; Hyeryeon Jung; Darlene Mae Ortiz; Hyun Jun Lee; Emad Alyan; Edmund Wascher; Stephan Getzmann; Mikyung Kim; Kyeong‑Man Kim; Eugene C. Yi; et al. (Molecular Neurobiology, 2025)
Attention-deficit/hyperactivity disorder, or ADHD, is a neurodevelopmental disorder with poorly understood molecular mechanisms. Recent studies have proposed that gene expression involved in regulating synaptic transmission in the striatum may play a role in ADHD pathogenesis. To explore the molecular basis of ADHD, we utilized proteomic analysis using whole striatal tissues from early adult thyroid hormone-responsive protein-overexpressing (THRSP-OE) mice, which displayed defining characteristics of predominantly inattentive ADHD (ADHD-PI). We focused on the striatal brain region due to its critical role in the regulation of attention, motivation, and reward processing. Moreover, the striatum modulates dopaminergic pathways that are known to be impaired in ADHD. Our analysis revealed an innate overexpression of Snap25 protein in THRSP-OE mice, indicating possible alterations in the SNARE protein complex and potential neurotransmitter dysregulation. Furthermore, a binding affinity study showed reduced dopamine D1 receptor binding concentrations and pronounced low dopamine levels in THRSP-OE mice. Repeated seven-day injections of methylphenidate improved the low dopamine levels, reducing the EEG theta/beta ratio in this animal model. These findings suggest new markers specific to the ADHD-PI presentation and further support the role of Snap25 dysregulation and possible SNARE protein complex alterations in ADHD-PI.

Long term assessment of SARS-CoV-2 in wastewater and the transition to evaluate additional viral targets - Ayaaz Amirali; Mark E. Sharkey; Shruti Choudhary; Kristina M. Babler; Cynthia C. Beaver; Pratim Biswas; Kate R. Bowie; Taylor Burke; Benjamin B. Currall; George S. Grills; Hannah G. Healy; Alexander G. Lucaci; et al. (Science of The Total Environment, 2025)

Signatures of Polar Vortex Weakening in the MLTI: A Review - V. L. Harvey; D. Aggarwal; E. Becker; M. Bittner; B. Funke; L. Goncharenko; J. Jia; R. Lieberman; H.-L. Liu; V. Maliniemi; A. Marchaudon; H. Nesse; et al. (Surveys in Geophysics, 2025)
This paper is a collaborative effort that originated at the International Space Science Institute Workshop on “Physical links between Weather and Climate in Space and the Lower Atmosphere” held 22–26 January 2024. Many scientists attended that workshop and contributed their expertise related to polar vortex impacts on upper atmosphere variability. This paper summarizes well-known and newly reported signatures of polar vortex weakening on mesosphere–lower-thermosphere (MLT) temperature, winds, composition, planetary waves, gravity waves, tides, and ionospheric foF2. A variety of observational and modeling results are shown and are consistent with previously published variations in the dynamical and chemical state of the MLT and ionosphere during weak vortex events. We present Superposed Epoch Analysis (SEA) of upper atmosphere diagnostics and phenomena where day 0 is the onset of major SSWs. We also present SEAs where day 0 is the onset of stratopause warmings followed by elevated stratopause events. Our goal in performing two SEAs is to test the sensitivity of 10 hPa versus 1 hPa winds to predict upper atmosphere variability. Results suggest that zonal winds and the semidiurnal migrating solar tide (SW2) in the MLT are more sensitive to zonal wind reversals at 1 hPa rather than 10 hPa. Alternatively, the non-migrating DW2 tide in the equatorial upper mesosphere is best predicted by planetary wave-1 amplitudes in the winter high-latitude upper stratosphere rather than zonal wind reversals. A notable aspect of both SEAs is extremely large event-to-event variability in all diagnostics. Thus, conclusions drawn based on any one event are less robust than those based on many events.

Skyglow increases cyanobacteria abundance and organic matter cycling in lakes - Jeremy Fonvielle; Lukas Thuile Bistarelli; Yile Tao; Jason N. Woodhouse; Tom Shatwell; Luis A. Villalba; Stella A. Berger; Christopher C.M. Kyba; Jens C. Nejstgaard; Andreas Jechow; Franziska Kupprat; Susanne Stephan; et al. (Water Research, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Fusion of food profiling data from very different analytical techniques - Kim C Brettschneider; Stephan Seifert (Current Opinion in Food Science, 2025)

Putting seedlings on the map: Trade‐offs in demographic rates between ontogenetic size classes in five tropical forests - Stephan Kambach; Helge Bruelheide; Liza S. Comita; Richard Condit; S. Joseph Wright; Salomón Aguilar; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; Nancy C. Garwood; Stephen P. Hubbell; Pei‐Jen Luo; Margaret R. Metz; et al. (Ecology, 2025)
All species must partition resources among the processes that underly growth, survival, and reproduction. The resulting demographic trade‐offs constrain the range of viable life‐history strategies and are hypothesized to promote local coexistence. Tropical forests pose ideal systems to study demographic trade‐offs as they have a high diversity of coexisting tree species whose life‐history strategies tend to align along two orthogonal axes of variation: a growth–survival trade‐off that separates species with fast growth from species with high survival and a stature–recruitment trade‐off that separates species that achieve large stature from species with high recruitment. As these trade‐offs have typically been explored for trees ≥1 cm dbh, it is unclear how species' growth and survival during earliest seedling stages are related to the trade‐offs for trees ≥1 cm dbh. Here, we used principal components and correlation analyses to (1) determine the main demographic trade‐offs among seed‐to‐seedling transition rates and growth and survival rates from the seedling to overstory size classes of 1188 tree species from large‐scale forest dynamics plots in Panama, Puerto Rico, Ecuador, Taiwan, and Malaysia and (2) quantify the predictive power of maximum dbh, wood density, seed mass, and specific leaf area for species' position along these demographic trade‐off gradients. In four out of five forests, the growth–survival trade‐off was the most important demographic trade‐off and encompassed growth and survival of both seedlings and trees ≥1 cm dbh. The second most important trade‐off separated species with relatively fast growth and high survival at the seedling stage from species with relatively fast growth and high survival ≥1 cm dbh. The relationship between seed‐to‐seedling transition rates and these two trade‐off aces differed between sites. All four traits were significant predictors for species' position along the two trade‐off gradients, albeit with varying importance. We concluded that, after accounting for the species' position along the growth–survival trade‐off, tree species tend to trade off growth and survival at the seedling with later life stages. This ontogenetic trade‐off offers a mechanistic explanation for the stature–recruitment trade‐off that constitutes an additional ontogenetic dimension of life‐history variation in species‐rich ecosystems.

Economics-constrained tidal turbine array layout optimisation at the Putuoshan–Hulu island waterway - Can Zhang; Xiaoming Cheng; Athanasios Angeloudis; Stephan C. Kramer; Chengsheng Wu; Ying Chen; Matthew D. Piggott (Ocean Engineering, 2024)

Size‐selective harvesting drives genomic shifts in a harvested population - Daniel E. Sadler; Tiina Sävilammi; Stephan N. van Dijk; Phillip C. Watts; Silva Uusi‐Heikkilä (Journal of Fish Biology, 2024)
Overfishing not only drastically reduces the number of fish in an exploited population but is also often selective for body size by removing the largest individuals from a population. Here, we study experimentally the evolutionary effects of size‐selective harvesting using whole‐genome sequencing on a model organism, the zebrafish ( Danio rerio ). We demonstrate genomic shifts in the populations exposed to size‐selective harvesting for five generations and show reduced genetic diversity in all harvested lines, including the control line (non‐size‐selected). We also determine differences in groups of genes related to certain gene ontology annotations between size‐selectively harvested lines, with enrichment in nervous system related genes in the large‐selected lines. Our results illuminate the biological processes underlying fisheries‐induced genetic changes and hence contribute toward the understanding of the changes potentially associated with the vulnerability of an exploited population to future stressors.

WILMO: an automated profiling system for coastal waters - Stephan C. Deschner; Gero Bojens; Kadir Orhan; Afifah Nasukha; Wolfgang Voigt (Frontiers in Marine Science, 2024)
Stationary in situ measurements conducted in close proximity to the shoreline present unique challenges. The shallow depth, automated profiling and accessibility for maintenance, particularly in the context of biofouling, are key considerations. The WInch for Long-term MOnitoring (WILMO), a solution designed to meet these requirements, is therefore presented. The fully automated system keeps the sensitive devices outside of the water until a profiling cycle is initiated, reducing the available settling time for species on the surface of the sensors. The design leverages common hardware and is structured in distinct units. This feature facilitates the interchangeability of individual hardware components and the implementation of a unifying software system capable of simultaneously managing all elements of WILMO. Using wireless broadband communications, WILMO can be fully controlled remotely, allowing for adjustments to the setup and monitoring of system functionality through a special web interface. The data are transmitted to a server with adjustable frequency and a post processing tool prepares them for analysis. The system underwent rigorous testing and demonstrated effective performance in northern Bali, Indonesia, between March and December 2022, gathering physical and biogeochemical time series data. The consistency of the data is validated through comparison with other instruments to ensure data quality. The results obtained are employed to ascertain the suitability of the special flow velocity sensor in this context. WILMO is a demonstrably reliable device, easily manageable and perfectly suited for long-term coastal monitoring.

Phylogenomics and biogeography of sawflies and woodwasps (Hymenoptera, Symphyta) - Saskia Wutke; Stephan M. Blank; Jean-Luc Boevé; Brant C. Faircloth; Frank Koch; Catherine R. Linnen; Tobias Malm; Gengyun Niu; Marko Prous; Nathan M. Schiff; Stefan Schmidt; Andreas Taeger; et al. (Molecular Phylogenetics and Evolution, 2024)

No general support for functional diversity enhancing resilience across terrestrial plant communities - Lucrecia Lipoma; Stephan Kambach; Sandra Díaz; Francesco María Sabatini; Gabriella Damasceno; Jens Kattge; Christian Wirth; Scott R. Abella; Carl Beierkuhnlein; Travis R. Belote; Markus Bernhardt‐Römermann; Dylan Craven; et al. (Global Ecology and Biogeography, 2024)
Aim Understanding the mechanisms promoting resilience in plant communities is crucial in times of increasing disturbance and global environmental change. Here, we present the first meta‐analysis evaluating the relationship between functional diversity and resilience of plant communities. Specifically, we tested whether the resilience of plant communities is positively correlated with interspecific trait variation (following the niche complementarity hypothesis) and the dominance of acquisitive and small‐size species (following the mass ratio hypothesis), and for the context‐dependent effects of ecological and methodological differences across studies. Location Global. Time Period 2004–2021. Major Taxa Studied Vascular plants. Methods We compiled a dataset of 69 independent sites from 26 studies that have quantified resilience. For each site, we calculated functional diversity indices based on the floristic composition and functional traits of the plant community (obtained from the TRY database) which we correlated with resilience of biomass and floristic composition. After transforming correlation coefficients to Fisher's Z ‐scores, we conducted a hierarchical meta‐analysis, using a multilevel random‐effects model that accounted for the non‐independence of multiple effect sizes and the effects of ecological and methodological moderators. Results In general, we found no positive functional diversity–resilience relationships of grand mean effect sizes. In contrast to our expectations, we encountered a negative relationship between resilience and trait variety, especially in woody ecosystems, whereas there was a positive relationship between resilience and the dominance of acquisitive species in herbaceous ecosystems. Finally, the functional diversity–resilience relationships were strongly affected by both ecological (biome and disturbance properties) and methodological (temporal scale, study design and resilience metric) characteristics. Main Conclusions We rejected our hypothesis of a general positive functional diversity–resilience relationship. In addition to strong context dependency, we propose that idiosyncratic effects of single resident species present in the communities before the disturbances and biological legacies could play major roles in the resilience of terrestrial plant communities.

A new potent peptide blocker, from Poecilotheria subfusca spider, of the human Cav1.2 channel subtype - Tânia C. Gonçalves; Michel De Waard; Michael Kurz; Stephan De Waard; Camille Sanson; Jérôme Montnach; Françoise Chesney; Rémy Béroud; Denis Servent; Michel Partiseti; Jean-Marie Chambard; Evelyne Benoit (Toxicon, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Accounting for nutrition-related health impacts in food life cycle assessment: insights from an expert workshop - Laura Scherer; Nicole Tichenor Blackstone; Zach Conrad; Victor L. Fulgoni, III; John C. Mathers; Jolieke C. van der Pols; Walter Willett; Peter Fantke; Stephan Pfister; Katerina S. Stylianou; Bo P. Weidema; Llorenç Milà i Canals; et al. (The International Journal of Life Cycle Assessment, 2024)
Sub-optimal dietary patterns make major contributions to the Global Burden of Disease and are among the most pressing issues affecting human health. Consequently, they are key to consider when assessing the human health and other environmental impacts of foods and diets within life cycle assessments. The UN Environment Life Cycle Initiative convened a task force on nutrition-related human health impacts as part of the Global Life Cycle Impact Assessment Method (GLAM) project. The health impacts of dietary patterns can be expressed in disability-adjusted life years (DALYs), in line with reporting human health impacts of other impact categories within the life cycle impact assessment (LCIA) framework. The task force held a workshop with nutrition experts to receive guidance in its process to develop a consensus-based impact assessment framework for addressing nutrition-related health impacts in LCIA. The workshop aimed to (1) evaluate the general assessment framework, (2) discuss scientific questions for quantifying human health impacts from nutrition for food items and diets, and (3) provide initial guidance for further development. The proposed framework based on the Global Burden of Disease (GBD) risk ratios was regarded as a good starting point to assess the relative health risks of the general population, provided that the dietary context is considered and several limitations, such as incomplete disease coverage, are acknowledged. The experts advised against a potentially misleading use of adult-derived dietary risk factors for children. To improve global coverage of the GLAM framework, it is important to consider a wider range of dietary patterns. The experts also recommended using a metric complementary to DALYs, such as nutrient adequacy, also considering, e.g., vitamin A and iron, to complement the assessment.

A mouthless late‐term coach whipray Himantura uarnak embryo (Elasmobranchii, Dasyatidae) has implications for our understanding of matrotrophy in chondrichthyans - Aaron C. Henderson; Stephan Bruns; Shamsa Al Hameli (Journal of Fish Biology, 2024)
Maternal nutrient provisioning occurs in most live‐bearing chondrichthyan lineages. It is particularly conspicuous in the Myliobatiformes, whereby the endometrium secretes a nutrient‐rich histotroph that is utilized by the developing embryo. The occurrence of a deformed and mouthless, late‐term myliobatiform embryo is described here, demonstrating that the direct, oral ingestion of histotroph is not obligatory in these animals.

Understanding diel bioaerosol patterns in mold-affected buildings through metagenomic surveillance - Irvan Luhung; Serene B.Y. Lim; Akira Uchida; Yee Hui Lim; Kenny J.X. Lau; Premkrishnan Balakrishnan; Stephan C. Schuster (Building and Environment, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

A wandering wedgefish illustrates the need for cooperative elasmobranch conservation in the Arabian Gulf - Stephan Bruns; Shamsa Al Hameli; Erik Sulanke; Aaron C. Henderson (Environmental Biology of Fishes, 2024)
The smoothnose wedgefish Rhynchobatus laevis , a shark-like ray classified as Critically Endangered by the International Union for Conservation of Nature, has received limited research attention. To address the knowledge gaps in its spatial behaviour, this study utilised satellite monitoring of a fortuitously captured female over a 51-day period in the Arabian Gulf. Based on the resulting movement track, the individual covered a minimum distance of 712 km, traversing the exclusive economic zones of three different countries. Its track began in the United Arab Emirates, from where it headed north, entering Iranian waters, where it spent most of its time, before continuing westward across the Gulf and eventually reaching Qatari waters. Novel insights into its behaviour revealed an observation of rapid ascents over the study period. Although both diurnal and nocturnal ascents were observed, they occurred predominantly during nocturnal periods. Contrary to the prevailing belief that wedgefish are bottom-associated, the study animal spent a considerable amount of time in the water column. The use of various depths in both nearshore and offshore waters highlights elevated susceptibility to multiple types of fishing gear. This underscores the need for an international cooperative approach to the management and conservation of shark-like rays in the Arabian Gulf.

Ground and Space-based response of the ionosphere during the geomagnetic storm of 02–06 November 2021 over the low-latitudes across different longitudes - Sharon Aol; Valence Habyarimana; Patrick Mungufeni; Stephan C. Buchert; John Bosco Habarulema (Advances in Space Research, 2024)

On the role of methyl groups in the molecular architectures of mesophase pitches - Aparna Annamraju; Gang Seob Jung; Samarthya Bhagia; Joshua T. Damron; Matthew R. Ryder; Mark A. Arnould; Ercan Cakmak; Frederic Vautard; Ryan M. Paul; Stephan Irle; Nidia C. Gallego; Edgar Lara Curzio (Fuel, 2024)

Coupled optical-electric monitoring of charge percolation events in carbon flow-electrodes - Maria C. Padligur; Christian J. Linnartz; Stephan Zimmer; John Linkhorst; Matthias Wessling (Chemical Engineering Journal, 2024)

Partitioning of highly siderophile elements between monosulfide solid solution and sulfide melt at high pressures - Raúl O. C. Fonseca; Christopher Beyer; Thilo Bissbort; Rebecca Hartmann; Stephan Schuth (Contributions to Mineralogy and Petrology, 2024)
Base metal sulfides (Fe–Ni–Cu–S) are ubiquitous phases in mantle and subduction-related lithologies. Sulfides in the mantle often melt incongruently, which leads to the production of a Cu–Ni-rich sulfide melt and a solid residue called monosulfide solid solution (mss). Even though peridotite-hosted sulfides, which tend to be more Ni-rich, are likely completely molten at mantle potential temperatures, the same is not true for eclogite-hosted Ni-poor, Fe-rich sulfides. Because of this, solid crystalline mss may persist at higher pressures and equilibrate with co-existing sulfide melt along colder geotherms, like those associated with subduction zones. Because highly siderophile elements (HSE—Pt, Pd, Rh, Ru, Os, Ir, and Re) are known to fractionate as a result of mss/sulfide-melt equilibrium, the persistence of an mss/sulfide-melt assemblage to higher pressures may lead to the fractionation of these elements during the subduction process. In this contribution, we carried out an experimental investigation of the partitioning behavior of the HSE, as well as Cu and Ni, between mss and sulfide melt over a pressure and temperature range relevant to equilibration between Earth’s surface and transition zone depths (0.1 MPa to 14 GPa; 930–1530 $$^{° }$$ ∘ C), and variable Ni contents in sulfide. Results show that at higher pressures, the HSE are considerably less fractionated as a result of mss and sulfide melt equilibrium compared to lower pressure conditions. This is exemplified by a lowering of the $$D_{i}^mss/melt$$ D i mss / melt for the more compatible HSE (Ru, Os, Ir, Rh and Re) from around 10 at 0.1 MPa to just above or below unity at 14 GPa. Moreover, the higher the Ni content of the bulk sulfide assemblage, the larger the degree of change in the magnitude of HSE fractionation seen over the pressure range studied. The exchange coefficient ( $$K_D^{Ru-Pt}$$ K D Ru - Pt ) between highly compatible HSE (Ru) and less compatible Pt illustrates a notable contrast. In the Ni-poor composition (E1), $$K_D^{Ru-Pt}$$ K D Ru - Pt changes from 27 at 0.1 MPa to 6 at 14 GPa. In contrast, the Ni-rich composition exhibits a broader range, with $$K_D^{Ru-Pt}$$ K D Ru - Pt ranging from 150 to 17 across the same pressure interval. Our results highlight key differences between experimental data obtained at lower and higher pressure, and how composition, namely the Ni content of sulfide, affects HSE partitioning behavior.

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Heritable differences in abundance of bacterial rhizosphere taxa are correlated with fungal necrotrophic pathogen resistance - Cloe S. Pogoda; Kyle G. Keepers; Stephan Reinert; Zahirul I. Talukder; Brian C. Smart; Ziv Attia; Jason A. Corwin; Kennedy L. Money; Erin C. E. Collier‐zans; William Underwood; Thomas J. Gulya; C. Alisha Quandt; et al. (Molecular Ecology, 2024)
Host–microbe interactions are increasingly recognized as important drivers of organismal health, growth, longevity and community‐scale ecological processes. However, less is known about how genetic variation affects hosts' associated microbiomes and downstream phenotypes. We demonstrate that sunflower ( Helianthus annuus ) harbours substantial, heritable variation in microbial communities under field conditions. We show that microbial communities co‐vary with heritable variation in resistance to root infection caused by the necrotrophic pathogen Sclerotinia sclerotiorum and that plants grown in autoclaved soil showed almost complete elimination of pathogen resistance. Association mapping suggests at least 59 genetic locations with effects on both microbial relative abundance and Sclerotinia resistance. Although the genetic architecture appears quantitative, we have elucidated previously unexplained genetic variation for resistance to this pathogen. We identify new targets for plant breeding and demonstrate the potential for heritable microbial associations to play important roles in defence in natural and human‐altered environments.

Lake browning counteracts cyanobacteria responses to nutrients: Evidence from phytoplankton dynamics in large enclosure experiments and comprehensive observational data - Anne Lyche Solheim; Hege Gundersen; Ute Mischke; Birger Skjelbred; Jens C. Nejstgaard; Alexis L. N. Guislain; Erik Sperfeld; Darren P. Giling; Sigrid Haande; Andreas Ballot; S. Jannicke Moe; Susanne Stephan; et al. (Global Change Biology, 2024)
Lakes worldwide are affected by multiple stressors, including climate change. This includes massive loading of both nutrients and humic substances to lakes during extreme weather events, which also may disrupt thermal stratification. Since multi‐stressor effects vary widely in space and time, their combined ecological impacts remain difficult to predict. Therefore, we combined two consecutive large enclosure experiments with a comprehensive time‐series and a broad‐scale field survey to unravel the combined effects of storm‐induced lake browning, nutrient enrichment and deep mixing on phytoplankton communities, focusing particularly on potentially toxic cyanobacterial blooms. The experimental results revealed that browning counteracted the stimulating effect of nutrients on phytoplankton and caused a shift from phototrophic cyanobacteria and chlorophytes to mixotrophic cryptophytes. Light limitation by browning was identified as the likely mechanism underlying this response. Deep‐mixing increased microcystin concentrations in clear nutrient‐enriched enclosures, caused by upwelling of a metalimnetic Planktothrix rubescens population. Monitoring data from a 25‐year time‐series of a eutrophic lake and from 588 northern European lakes corroborate the experimental results: Browning suppresses cyanobacteria in terms of both biovolume and proportion of the total phytoplankton biovolume. Both the experimental and observational results indicated a lower total phosphorus threshold for cyanobacterial bloom development in clearwater lakes (10–20 μg P L −1 ) than in humic lakes (20–30 μg P L −1 ). This finding provides management guidance for lakes receiving more nutrients and humic substances due to more frequent extreme weather events.

Monkeypox viral nucleic acids detected using both DNA and RNA extraction workflows - Mark E. Sharkey; Kristina M. Babler; Bhavarth S. Shukla; Samantha M. Abelson; Bader Alsuliman; Ayaaz Amirali; Samuel Comerford; George S. Grills; Naresh Kumar; Jennifer Laine; Jisue Lee; Walter E. Lamar; et al. (Science of The Total Environment, 2023)

Unified depth-limited wave breaking detection and dissipation in fully nonlinear potential flow models - Sunil Mohanlal; Jeffrey C. Harris; Marissa L. Yates; Stephan T. Grilli (Coastal Engineering, 2023)

Light stable Cr isotope compositions of mid-ocean ridge basalts: Implications for mantle source composition - Luise J. Wagner; Ilka C. Kleinhanns; Maria I. Varas-Reus; Carolina Rosca; Stephan König; Wolfgang Bach; Ronny Schoenberg (Geochimica et Cosmochimica Acta, 2023)

Occurrence of the endangered whitespotted eagle ray Aetobatus narinari around the Lesser Antilles island of Saint Kitts: a photo-identification study - Anne Conan; Michelle M. Dennis; Kathleen Gilbert; Eva Lenain; Stephan Bruns; Aaron C. Henderson (Environmental Biology of Fishes, 2023)

CME propagation through the heliosphere: Status and future of observations and model development - Manuela Temmer; Camilla Scolini; Ian G. Richardson; Stephan G. Heinemann; Evangelos Paouris; Angelos Vourlidas; Mario M. Bisi; N. Al-Haddad; T. Amerstorfer; L. Barnard; D. Burešová; S.J. Hofmeister; et al. (Advances in Space Research, 2023)

Herbaceous vegetation responses to experimental fire in savannas and forests depend on biome and climate - Zachary J. Gold; Adam F. A. Pellegrini; Tyler K. Refsland; Romina J. Andrioli; Marlin L. Bowles; Dale G. Brockway; Neil Burrows; Augusto C. Franco; Steve W. Hallgren; Sarah E. Hobbie; William A. Hoffmann; Kevin P. Kirkman; et al. (Ecology Letters, 2023)
Fire–vegetation feedbacks potentially maintain global savanna and forest distributions. Accordingly, vegetation in savanna and forest ecosystems should have differential responses to fire, but fire response data for herbaceous vegetation have yet to be synthesized across biomes. Here, we examined herbaceous vegetation responses to experimental fire at 30 sites spanning four continents. Across a variety of metrics, herbaceous vegetation increased in abundance where fire was applied, with larger responses to fire in wetter and in cooler and/or less seasonal systems. Compared to forests, savannas were associated with a 4.8 (±0.4) times larger difference in herbaceous vegetation abundance for burned versus unburned plots. In particular, grass cover decreased with fire exclusion in savannas, largely via decreases in C 4 grass cover, whereas changes in fire frequency had a relatively weak effect on grass cover in forests. These differential responses underscore the importance of fire for maintaining the vegetation structure of savannas and forests.

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

An advanced towed CTD chain for physical-biological high resolution in situ upper ocean measurements - Thomas Kock; Burkard Baschek; Florian Wobbe; Martina Heineke; Rolf Riethmueller; Stephan C. Deschner; Gerd Seidel; Paulo H. R. Calil (Frontiers in Marine Science, 2023)
Submesoscale eddies, fronts, and filaments are ubiquitous in the upper ocean and play an important role in biogeochemical and mixing processes as well as in the energy budget. To capture the high spatial variability of submesoscale processes, it is desirable to simultaneously resolve the vertical and horizontal gradients of hydrographic properties on scales of 10 m to 10 km. We present a revised towed CTD chain, for rapid quasi-synoptic in situ measurements of submesoscale oceanographic features, that is lighter, more robust and scientifically more useful than previous towed CTD chains. This new instrument provides a horizontal resolution of O (1 m) and can be towed at speeds of up to 5 ms -1 for measurements of the upper 100 m of the water column while providing a reasonable vertical resolution of O (1 m – 10 m). Individual CTD probes are equipped with temperature, conductivity, pressure and either rapid response dissolved oxygen or fluorescence sensors at multiple depths, enabling both hydrographic and biogeochemical studies at high resolution. A flexible probe hardware allows either real-time data collection or internal data logging for offline post-processing. Finally, we outline the necessary post-processing steps and provide data examples. With the presented data examples we show and conclude that the advanced towed CTD chain is a flexible and lightweight take on the towed CTD chain concept. It can easily be adapted to scientific needs and provides high quality very high resolution oceanographic data.

Degradation rates influence the ability of composite samples to represent 24-hourly means of SARS-CoV-2 and other microbiological target measures in wastewater - Kristina M. Babler; Mark E. Sharkey; Samantha Abelson; Ayaaz Amirali; Aymara Benitez; Gabriella A. Cosculluela; George S. Grills; Naresh Kumar; Jennifer Laine; Walter Lamar; Erik D. Lamm; Jiangnan Lyu; et al. (Science of The Total Environment, 2023)

Towards a fully unstructured ocean model for ice shelf cavity environments: Model development and verification using the Firedrake finite element framework - William I. Scott; Stephan C. Kramer; Paul R. Holland; Keith W. Nicholls; Martin J. Siegert; Matthew D. Piggott (Ocean Modelling, 2023)

Tree insect pests and pathogens: a global systematic review of their impacts in urban areas - Susanne Raum; C. Matilda Collins; Julie Urquhart; Clive Potter; Stephan Pauleit; Monika Egerer (Urban Ecosystems, 2023)
Trees contribute greatly to urban environments and human well-being, yet relatively little is known about the extent to which a rising incidence of tree insect pests and pathogens may be affecting these contributions. To address this issue, we undertook a systematic review and synthesis of the diverse global empirical evidence on the impacts of urban tree insect pests and pathogens, using bibliographic databases. Following screening and appraisal of over 3000 articles from a wide range of fields, 100 studies from 28 countries, spanning 1979–2021, were conceptually sorted into a three-part framework: (1) environmental impacts, representing 95 of the studies, including those reporting on tree damage, mortality, reduced growth, and changes in tree function; (2) social impacts were reported by 35 of studies, including on aesthetics, human health, and safety hazards; and (3) economic impacts, reported in 24 of studies, including on costs of pest management, and economic losses. There has been a considerable increase in urban impact studies since 2011. Evidence gaps exist on impacts on climate-regulating capacity, including temperature regulation, water retention, soil erosion, and wind protection, but also on specific hazards, nuisances, human well-being, property damages, and hazard liabilities. As a knowledge synthesis, this article presents the best available evidence of urban tree insect / pathogen impacts to guide policy, management and further research. It will enable us to better forecast how growing threats will affect the urban forest and plan for these eventualities.

Smooth muscle “microsphincters” in the gastric mucosa of stingrays (Elasmobranchii, Dasyatidae) - Aaron C. Henderson; Stephan Bruns; Shamsa Al Hameli (Journal of Fish Biology, 2023)
The occurrence of smooth muscle sphincters around gastric gland tubules in the cardiac stomach of some elasmobranch species is reported for the first time. These “microsphincters” took the form of a twisted torus, approximately 12–16 muscle fibres thick, that could fully constrict the gland tubules. However, their inconsistent positioning does not suggest a role in partitioning the tubules from the stomach lumen or in modulating secretory activity. Further research is required to ascertain the full taxonomic occurrence of these structures across the Elasmobranchii and to elucidate their function.

Standards of NGS Data Sharing and Analysis in Ataxias: Recommendations by the NGS Working Group of the Ataxia Global Initiative - Danique Beijer; Brent L. Fogel; Sergi Beltran; Matt C. Danzi; Andrea H. Németh; Stephan Züchner; Matthis Synofzik; Astrid Adarmes; Saud Alhusaini; Mahmoud Reza Ashrafi; Luis Bataller; Enrico Bertini; et al. (The Cerebellum, 2023)
The Ataxia Global Initiative (AGI) is a worldwide multi-stakeholder research platform to systematically enhance trial-readiness in degenerative ataxias. The next-generation sequencing (NGS) working group of the AGI aims to improve methods, platforms, and international standards for ataxia NGS analysis and data sharing, ultimately allowing to increase the number of genetically ataxia patients amenable for natural history and treatment trials. Despite extensive implementation of NGS for ataxia patients in clinical and research settings, the diagnostic gap remains sizeable, as approximately 50% of patients with hereditary ataxia remain genetically undiagnosed. One current shortcoming is the fragmentation of patients and NGS datasets on different analysis platforms and databases around the world. The AGI NGS working group in collaboration with the AGI associated research platforms—CAGC, GENESIS, and RD-Connect GPAP—provides clinicians and scientists access to user-friendly and adaptable interfaces to analyze genome-scale patient data. These platforms also foster collaboration within the ataxia community. These efforts and tools have led to the diagnosis of > 500 ataxia patients and the discovery of > 30 novel ataxia genes. Here, the AGI NGS working group presents their consensus recommendations for NGS data sharing initiatives in the ataxia field, focusing on harmonized NGS variant analysis and standardized clinical and metadata collection, combined with collaborative data and analysis tool sharing across platforms.

Intermittent instability is widespread in plankton communities - Tanya L. Rogers; Stephan B. Munch; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2023)
Chaotic dynamics appear to be prevalent in short‐lived organisms including plankton and may limit long‐term predictability. However, few studies have explored how dynamical stability varies through time, across space and at different taxonomic resolutions. Using plankton time series data from 17 lakes and 4 marine sites, we found seasonal patterns of local instability in many species, that short‐term predictability was related to local instability, and that local instability occurred most often in the spring, associated with periods of high growth. Taxonomic aggregates were more stable and more predictable than finer groupings. Across sites, higher latitude locations had higher Lyapunov exponents and greater seasonality in local instability, but only at coarser taxonomic resolution. Overall, these results suggest that prediction accuracy, sensitivity to change and management efficacy may be greater at certain times of year and that prediction will be more feasible for taxonomic aggregates.

Sediment gravity flow frequency offshore central California diminished significantly following the Last Glacial Maximum - Stephen C. Dobbs; Charles K. Paull; Eve M. Lundsten; Roberto Gwiazda; David W. Caress; Mary McGann; Marianne M. Coholich; Maureen A. L. Walton; Nora M. Nieminski; Tim McHargue; Stephan A. Graham (Frontiers in Marine Science, 2023)
A high-resolution multibeam survey from a portion of the San Simeon Channel (offshore Morro Bay, California) captured a zone of recurring troughs and ridges adjacent to prominent submarine meander bends. Through an integrated study using surveying data, sediment core analysis, radiocarbon dating, and stable isotope measurements, we hypothesize that turbidity current event frequency was higher during the late Pleistocene than at present conditions. We speculate that the rise in sea-level following the Last Glacial Maximum sequestered sedimentation largely to the shelf during the Holocene. This work suggests that the occurrence of sediment gravity flows in this region, particularly away from any submarine channels, is appreciably lower than at times of continental shelf subaerial exposure.

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

Predicting COVID-19 cases using SARS-CoV-2 RNA in air, surface swab and wastewater samples - Helena M. Solo-Gabriele; Shelja Kumar; Samantha Abelson; Johnathon Penso; Julio Contreras; Kristina M. Babler; Mark E. Sharkey; Alejandro M.A. Mantero; Walter E. Lamar; John J. Tallon; Erin Kobetz; Natasha Schaefer Solle; et al. (Science of The Total Environment, 2023)

Submerged marine towed instrument array: A theoretical investigation using Lagrange mechanics - Stephan C. Deschner; Thomas Kock; Heinz Schelwat; Burkard Baschek (Ocean Engineering, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Hybrid Lattice-Boltzmann-Potential Flow Simulations of Turbulent Flow around Submerged Structures - Christopher M. O’Reilly; Stephan T. Grilli; Christian F. Janßen; Jason M. Dahl; Jeffrey C. Harris (Journal of Marine Science and Engineering, 2022)
We report on the development and validation of a 3D hybrid Lattice Boltzmann Model (LBM), with Large Eddy Simulation (LES), to simulate the interactions of incompressible turbulent flows with ocean structures. The LBM is based on a perturbation method, in which the velocity and pressure are expressed as the sum of an inviscid flow and a viscous perturbation. The far- to near-field flow is assumed to be inviscid and represented by potential flow theory, which can be efficiently modeled with a Boundary Element Method (BEM). The near-field perturbation flow around structures is modeled by the Navier–Stokes (NS) equations, based on a Lattice Boltzmann Method (LBM) with a Large Eddy Simulation (LES) of the turbulence. In the paper, we present the hybrid model formulation, in which a modified LBM collision operator is introduced to simulate the viscous perturbation flow, resulting in a novel perturbation LBM (pLBM) approach. The pLBM is then extended for the simulation of turbulence using the LES and a wall model to represent the viscous/turbulent sub-layer near solid boundaries. The hybrid model is first validated by simulating turbulent flows over a flat plate, for moderate to large Reynolds number values, Re ∈[3.7×104;1.2×106]; the plate friction coefficient and near-field turbulence properties computed with the model are found to agree well with both experiments and direct NS simulations. We then simulate the flow past a NACA-0012 foil using a regular LBM-LES and the new hybrid pLBM-LES models with the wall model, for Re = 1.44×106. A good agreement is found for the computed lift and drag forces, and pressure distribution on the foil, with experiments and results of other numerical methods. Results obtained with the pLBM model are either nearly identical or slightly improved, relative to those of the standard LBM, but are obtained in a significantly smaller computational domain and hence at a much reduced computational cost, thus demonstrating the benefits of the new hybrid approach.

High-pressure phase relations in the system Fe–Ni–Cu–S up to 14 GPa: implications for the stability of sulfides in the earth’s upper mantle - Christopher Beyer; Thilo Bissbort; Rebecca Hartmann; Jasper Berndt; Stephan Klemme; Raúl O. C. Fonseca (Contributions to Mineralogy and Petrology, 2022)
Base metal sulfides (Fe–Ni–Cu–S) are ubiquitous phases in mantle and subduction-related lithologies. Sulfides in the mantle often melt incongruently, which leads to the production of a Cu–Ni-rich sulfide melt and leaves a solid residue called monosulfide solid solution (mss). However, the persistence of crystalline sulfide phases like mss in the Earth’s mantle at higher temperatures and pressures deep within the Earth has long been up for debate, as the presence of both mss and sulfide melt in mantle rocks implies the fractionation of chalcophile elements during mantle melting. Recent studies have shown that the average mantle sulfide (45 wt.% Fe, 16 wt.% Ni, 1 wt.% Cu, and 38 wt.% S), is fully molten at average mantle potential temperatures (1300–1400 $$^{° }$$ ∘ C) up to 8 GPa (ca. 240 km). However, sulfide inclusions found in diamonds show a broad compositional spectrum, ranging from Ni-poor and Fe-rich (eclogitic), to Ni-rich and Fe-poor sulfides (peridotitic), with their Cu contents being generally low. The wide compositional variety of diamond-hosted sulfide inclusions raises the possibility that results on the melting properties obtained from this average mantle sulfide compositional may not reflect that found in those inclusions. As such, further investigation of the melting properties of sulfides from a wide compositional range is necessary. Here, we present the results of an experimental study where the melting properties of typical sulfide compositions found in diamond inclusions associated with eclogites and peridotites have been determined. Experiments have been carried out between 0.1 MPa and 14 GPa, and between 920 and 1590 $$^{° }$$ ∘ C, on box muffle furnaces, end-loaded piston cylinder, and multi-anvil apparatuses. Results show that solid mss in Fe-rich, Ni-poor sulfide inclusions associated with eclogites persist to higher pressures and temperatures compared to their less-refractory, more Ni-rich peridotitic counterparts to the depth of the mantle transition zone (410 km depth). Our results have implications for the recycling of chalcophile elements during subduction-related processes and the entrapment of sulfides in diamonds.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Neuroinflammation in Primary Cultures of the Rat Spinal Dorsal Horn Is Attenuated in the Presence of Adipose Tissue–Derived Medicinal Signalling Cells (AdMSCs) in a Co-cultivation Model - Stephan Leisengang; Laura B. Heilen; Michele C. Klymiuk; Franz Nürnberger; Daniela Ott; Kathrin Wolf-Hofmann; Rüdiger Gerstberger; Christoph Rummel; Martin J. Schmidt; Stefan Arnhold; Joachim Roth (Molecular Neurobiology, 2022)
Neuroinflammation within the superficial dorsal horn (SDH) of the spinal cord induces inflammatory pain with symptoms of hyperalgesia and allodynia. Glial activation and production of inflammatory mediators (e.g. cytokines) is associated with modulation of nociceptive signalling. In this context, medicinal signalling cells, e.g. obtained from adipose tissue (AdMSCs), gained attention due to their capacity to modulate the inflammatory response in several diseases, e.g. spinal cord injury. We applied the recently established mixed neuroglial primary cell culture of the rat SDH to investigate effects of AdMSCs on the inflammatory response of SDH cells. Following establishment of a co-cultivation system, we performed specific bioassays for tumour necrosis factor alpha (TNFα) and interleukin (IL)-6, RT-qPCR and immunocytochemistry to detect changes in cytokine production and glial activation upon inflammatory stimulation with lipopolysaccharide (LPS). LPS-induced expression and release of pro-inflammatory cytokines (TNFα, IL-6) by SDH cells was significantly attenuated in the presence of AdMSCs. Further evidence for anti-inflammatory capacities of AdMSCs derived from a blunted LPS-induced TNFα/IL-10 expression ratio and suppressed nuclear translocation of the inflammatory transcription factor nuclear factor kappa B (NFκB) in SDH microglial cells. Expression of IL-10, transforming growth factor beta (TGF-β) and TNFα-stimulated gene-6 (TSG-6) was detected in AdMSCs, which are putative candidates for anti-inflammatory capacities of these cells. We present a novel co-cultivation system of AdMSCs with neuroglial primary cultures of the SDH to investigate immunomodulatory effects of AdMSCs at a cellular level.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Traits mediate niches and co‐occurrences of forest beetles in ways that differ among bioclimatic regions - Ryan C. Burner; Jörg G. Stephan; Lukas Drag; Tone Birkemoe; Jörg Muller; Tord Snäll; Otso Ovaskainen; Mária Potterf; Juha Siitonen; Olav Skarpaas; Inken Doerfler; Martin M. Gossner; et al. (Journal of Biogeography, 2021)
Aim The aim of this study was to investigate the role of traits in beetle community assembly and test for consistency in these effects among several bioclimatic regions. We asked (1) whether traits predicted species’ responses to environmental gradients (i.e. their niches), (2) whether these same traits could predict co‐occurrence patterns and (3) how consistent were niches and the role of traits among study regions. Location Boreal forests in Norway and Finland, temperate forests in Germany. Taxon Wood‐living (saproxylic) beetles. Methods We compiled capture records of 468 wood‐living beetle species from the three regions, along with nine morphological and ecological species traits. Eight climatic and forest covariates were also collected. We used Bayesian hierarchical joint species distribution models to estimate the influence of traits and phylogeny on species’ niches. We also tested for correlations between species associations and trait similarity. Finally, we compared species niches and the effects of traits among study regions. Results Traits explained some of the variability in species’ niches, but their effects differed among study regions. However, substantial phylogenetic signal in species niches implies that unmeasured but phylogenetically structured traits have a stronger effect. Degree of trait similarity was correlated with species associations but depended idiosyncratically on the trait and region. Species niches were much more consistent—widespread taxa often responded similarly to an environmental gradient in each region. Main conclusions The inconsistent effects of traits among regions limit their current use in understanding beetle community assembly. Phylogenetic signal in niches, however, implies that better predictive traits can eventually be identified. Consistency of species niches among regions means niches may remain relatively stable under future climate and land use changes; this lends credibility to predictive distribution models based on future climate projections but may imply that species’ scope for short‐term adaptation is limited.

The titin N2B and N2A regions: biomechanical and metabolic signaling hubs in cross-striated muscles - Robbert J. van der Pijl; Andrea A. Domenighetti; Farah Sheikh; Elisabeth Ehler; Coen A. C. Ottenheijm; Stephan Lange (Biophysical Reviews, 2021)
Muscle specific signaling has been shown to originate from myofilaments and their associated cellular structures, including the sarcomeres, costameres or the cardiac intercalated disc. Two signaling hubs that play important biomechanical roles for cardiac and/or skeletal muscle physiology are the N2B and N2A regions in the giant protein titin. Prominent proteins associated with these regions in titin are chaperones Hsp90 and αB-crystallin, members of the four-and-a-half LIM (FHL) and muscle ankyrin repeat protein (Ankrd) families, as well as thin filament-associated proteins, such as myopalladin. This review highlights biological roles and properties of the titin N2B and N2A regions in health and disease. Special emphasis is placed on functions of Ankrd and FHL proteins as mechanosensors that modulate muscle-specific signaling and muscle growth. This region of the sarcomere also emerged as a hotspot for the modulation of passive muscle mechanics through altered titin phosphorylation and splicing, as well as tethering mechanisms that link titin to the thin filament system.

Biochemistry and physiology of zebrafish photoreceptors - Jingjing Zang; Stephan C. F. Neuhauss (Pflügers Archiv - European Journal of Physiology, 2021)
All vertebrates share a canonical retina with light-sensitive photoreceptors in the outer retina. These photoreceptors are of two kinds: rods and cones, adapted to low and bright light conditions, respectively. They both show a peculiar morphology, with long outer segments, comprised of ordered stacks of disc-shaped membranes. These discs host numerous proteins, many of which contribute to the visual transduction cascade. This pathway converts the light stimulus into a biological signal, ultimately modulating synaptic transmission. Recently, the zebrafish ( Danio rerio ) has gained popularity for studying the function of vertebrate photoreceptors. In this review, we introduce this model system and its contribution to our understanding of photoreception with a focus on the cone visual transduction cascade.

Breeding for sustainable oilseed crop yield and quality in a changing climate - Ziv Attia; Cloe S. Pogoda; Stephan Reinert; Nolan C. Kane; Brent S. Hulke (Theoretical and Applied Genetics, 2021)

A tsunamigenic delta collapse and its associated tsunami deposits in and around Lake Sils, Switzerland - Valentin Nigg; Stephan Wohlwend; Michael Hilbe; Benjamin Bellwald; Stefano C. Fabbri; Gregory F. de Souza; Florian Donau; Reto Grischott; Michael Strasser; Flavio S. Anselmetti (Natural Hazards, 2021)
Large lacustrine mass movements and delta collapses are increasingly being considered as potential tsunamigenic sources and therefore hazardous for the population and infrastructure along lakeshores. Although historical reports document tsunami events in several lakes in Switzerland, and although the propagation of lake tsunamis has been studied by numerical wave modeling, only little is known about on- and offshore lacustrine tsunami deposits. In Lake Sils, Switzerland, a large prehistoric mass-movement deposit originating from the Isola Delta with a minimum estimated volume of 6.5 × 10 6 m 3 and a basinal thickness of > 6 m in the seismic record has been identified by previous studies and radiocarbon dated to around 700 Common Era. Here, we combine (i) comprehensive sedimentological investigation of sediment cores recovered from the on- and offshore settings, (ii) mineralogical fingerprinting of the inflows from key catchments to characterize sediment provenance, and (iii) numerical tsunami modeling, to test the hypothesis of a tsunamigenic delta collapse in Lake Sils. We observe a clastic event deposit consisting of coarse-grained, fining-upward sand overlying an organic-rich peat deposit in the shallow water. This layer thins and fines landward on the coastal plain. Toward the deeper water (20–40 m), the deposit transforms into a thicker and more heterogeneous sediment package with multiple sequences of fining-upward sand and a well-pronounced clay cap at the top. Radiocarbon dating of the peat underlying the event deposit yields a maximum age of 225–419 calibrated Common Era. The tsunami models, which indicate wave heights reaching up to 5 m, simulate areas of inundation that coincide with the location of event deposits. Based on our results, we propose that the historically undocumented Isola Delta collapse generated a basin-wide tsunami that inundated the lakeshore, transporting large amounts of unconsolidated sediment along the lakeshore toward the coastal plain and into the deeper lake basin.

Haploinsufficiency of the HIRA gene located in the 22q11 deletion syndrome region is associated with abnormal neurodevelopment and impaired dendritic outgrowth - Médéric Jeanne; Marie-Laure Vuillaume; Dévina C. Ung; Valerie E. Vancollie; Christel Wagner; Stephan C. Collins; Sandrine Vonwill; Damien Haye; Nora Chelloug; Rolph Pfundt; Joost Kummeling; Marie-Pierre Moizard; et al. (Human Genetics, 2021)

Cross-paradigm connectivity: reliability, stability, and utility - Hengyi Cao; Oliver Y. Chen; Sarah C. McEwen; Jennifer K. Forsyth; Dylan G. Gee; Carrie E. Bearden; Jean Addington; Bradley Goodyear; Kristin S. Cadenhead; Heline Mirzakhanian; Barbara A. Cornblatt; Ricardo E. Carrión; et al. (Brain Imaging and Behavior, 2021)

Genetic loci underlying quantitative resistance to necrotrophic pathogens Sclerotinia and Diaporthe (Phomopsis), and correlated resistance to both pathogens - Cloe S. Pogoda; Stephan Reinert; Zahirul I. Talukder; Ziv Attia; Erin C. E. Collier-zans; Thomas J. Gulya; Nolan C. Kane; Brent S. Hulke (Theoretical and Applied Genetics, 2021)

Importance of oxidation products in coumarin-mediated Fe(hydr)oxide mineral dissolution - Matthias Baune; Kyounglim Kang; Walter D. C. Schenkeveld; Stephan M. Kraemer; Heiko Hayen; Günther Weber (BioMetals, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Hydraulic niche utilization by larvae of the three Drusinae clades (Insecta: Trichoptera) - Johann Waringer; Simon Vitecek; Jan Martini; Carina Zittra; Stephan Handschuh; Ariane Vieira; Hendrik C. Kuhlmann (Biologia, 2020)
Hydraulic niche descriptors of final instar larvae of nine Drusus species (Trichoptera) were studied in small, spring-fed, first-order headwaters located in the Mühlviertel (Upper Austria), Koralpe (Carinthia, Austria), and in the Austrian and Italian Alps. The species investigated covered all three clades of Drusinae: the shredder clade ( Drusus franzi , D. alpinus ), the grazer clade ( D. biguttatus , D. chauvinianus , D. dudor , D. monticola ), and the filtering carnivore clade ( D. chrysotus , D. katagelastos , D. muelleri ). Flow velocity was measured at front center of 68 larvae, head upstream, on the top of mineral substrate particles at water depths of 10–30 mm, using a tripod-stabilized Micro propeller meter (propeller diameter = 10 mm). Each data series consisted of a sampled measurement lasting 30 s (measuring interval = 1 s). In total, 2040 single velocity measurements were taken. Instantaneous flow velocities and drag at the sites of the 68 larvae varied from 0 to 0.93 m s −1 and 0 to 8346 *10 −6 N, respectively. Flow velocities and drag between the three clades were highly significantly different ( p + 95% confidence limits) for the three clades were 0.09 + 0.00 m s −1 for the shredder, 0.25 + 0.00 m s −1 for the grazer, and 0.31 + 0.01 m s −1 for the filtering carnivore clade; the corresponding data for drag were (85 + 18)*10 −6 N, (422 + 61)*10 −6 N and (1125 + 83)*10 −6 N, respectively. Adhesive friction ranged from (41.07 + 53.03)*10 −6 N in D. franzi to (255.24 + 216.87)*10 −6 N in D. chrysotus . Except in D. franzi and D. dudor adhesive friction was always well below drag force, indicating that submerged weight alone was not sufficient to stabilize the larvae in their hydraulic environment. Reynolds numbers varied between 0 in D. franzi and D. alpinus , and 12,634 in D. katagelastos , with 7% of the total in the laminar ( R R = 500–2000), and 61% in the fully turbulent stage ( R > 2000). Froude numbers ( Fr ) varied from 0 to 2.97. The two Drusus species of the shredder clade and three out of four species of the grazer clade were exposed to subcritical Fr 1.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Hydraulic stress parameters of a cased caddis larva (Drusus biguttatus) using spatio-temporally filtered velocity measurements - Johann Waringer; Simon Vitecek; Jan Martini; Carina Zittra; Stephan Handschuh; Ariane Vieira; Hendrik C. Kuhlmann (Hydrobiologia, 2020)
By studying hydraulic stress parameters of larvae of the cased caddisfly Drusus biguttatus (Pictet, 1834) in a tributary of the Schwarze Sulm (Carinthia, Austria), we aimed on (1) detecting the flow properties of the spatio-temporally filtered velocity measurements taken, and (2) on defining the hydraulic niche of this caddisfly larva. For this, we took 31 measurement series lasting 30 to 300 s, yielding 2176 single velocity measurements. The probability density functions of the 31 data series were Gaussian or sub-Gaussian, and the mean recurrent interval between velocity maxima within a data series was only 15.00 s. As a consequence, the Trichoptera larvae studied have to face strong flow accelerations in short intervals which is a much higher stress than conventional mean velocity measurements would suggest. The hydraulic niche of Drusus biguttatus is defined by instantaneous flow velocities ranging from 0.04 to 0.69 m s −1 , by drag forces from 13 × 10 −6 to 3737 × 10 −6 N, by Froude numbers from 0.13 to 1.20, and mostly by Reynolds numbers > 2000. Under such conditions, only 5.1% of the drag force is compensated by submerged weight, whereas the remainder has to be counterbalanced by the active efforts of the larvae to remain attached to the substrate.

A baited remote underwater video system (BRUVS) assessment of elasmobranch diversity and abundance on the eastern Caicos Bank (Turks and Caicos Islands); an environment in transition - Stephan Bruns; Aaron C. Henderson (Environmental Biology of Fishes, 2020)

“A reference genome assembly and adaptive trait analysis of Castanea mollissima ‘Vanuxem,’ a source of resistance to chestnut blight in restoration breeding” - Margaret Staton; Charles Addo-Quaye; Nathaniel Cannon; Jiali Yu; Tetyana Zhebentyayeva; Matthew Huff; Nurul Islam-Faridi; Shenghua Fan; Laura L. Georgi; C. Dana Nelson; Emily Bellis; Sara Fitzsimmons; et al. (Tree Genetics & Genomes, 2020)

Trophic control changes with season and nutrient loading in lakes - Tanya L. Rogers; Stephan B. Munch; Simon D. Stewart; Eric P. Palkovacs; Alfredo Giron‐Nava; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2020)
Experiments have revealed much about top‐down and bottom‐up control in ecosystems, but manipulative experiments are limited in spatial and temporal scale. To obtain a more nuanced understanding of trophic control over large scales, we explored long‐term time‐series data from 13 globally distributed lakes and used empirical dynamic modelling to quantify interaction strengths between zooplankton and phytoplankton over time within and across lakes. Across all lakes, top‐down effects were associated with nutrients, switching from negative in mesotrophic lakes to positive in oligotrophic lakes. This result suggests that zooplankton nutrient recycling exceeds grazing pressure in nutrient‐limited systems. Within individual lakes, results were consistent with a ‘seasonal reset’ hypothesis in which top‐down and bottom‐up interactions varied seasonally and were both strongest at the beginning of the growing season. Thus, trophic control is not static, but varies with abiotic conditions – dynamics that only become evident when observing changes over large spatial and temporal scales.

The inverse autotransporters of Yersinia ruckeri , YrInv and YrIlm , contribute to biofilm formation and virulence - Agnieszka Wrobel; Athanasios Saragliadis; Jesús Pérez‐Ortega; Carolin Sittman; Stephan Göttig; Krystyna Liskiewicz; Maria Helle Spence; Kenneth Schneider; Jack C. Leo; Jesús Arenas; Dirk Linke (Environmental Microbiology, 2020)
Summary Yersinia ruckeri causes enteric redmouth disease (ERM) that mainly affects salmonid fishes and leads to significant economic losses in the aquaculture industry. An increasing number of outbreaks and the lack of effective vaccines against some serotypes necessitates novel measures to control ERM. Importantly, Y. ruckeri survives in the environment for long periods, presumably by forming biofilms. How the pathogen forms biofilms and which molecular factors are involved in this process, remains unclear. Yersinia ruckeri produces two surface‐exposed adhesins, belonging to the inverse autotransporters (IATs), called Y. ruckeri invasin (YrInv) and Y. ruckeri invasin‐like molecule (YrIlm). Here, we investigated whether YrInv and YrIlm play a role in biofilm formation and virulence. Functional assays revealed that YrInv and YrIlm promote biofilm formation on different abiotic substrates. Confocal microscopy revealed that they are involved in microcolony interaction and formation, respectively. The effect of both IATs on biofilm formation correlated with the presence of different biopolymers in the biofilm matrix, including extracellular DNA, RNA and proteins. Moreover, YrInv and YrIlm contributed to virulence in the Galleria mellonella infection model. Taken together, we propose that both IATs are possible targets for the development of novel diagnostic and preventative strategies to control ERM.

Complete Genome Sequence of Penicillium oxalicum Strain SGAir0226 Isolated from Outdoor Tropical Air in Singapore - Anjali Bansal Gupta; Nicolas E. Gaultier; Ngu War Aung; Rikky W. Purbojati; Elaine L. Oliveira; Anthony Wong; Deepa Panicker; Alexander Putra; Akira Uchida; Daniela I. Drautz-Moses; Stephan C. Schuster (Mycopathologia, 2020)

Whole-Genome Sequencing of Aspergillus terreus Species Complex - Mathangi Palanivel; Micheál Mac Aogáin; Rikky W. Purbojati; Akira Uchida; Ngu War Aung; Serene B. Y. Lim; Alexander Putra; Daniela I. Drautz-Moses; Shila Seaton; Thomas R. Rogers; Stephan C. Schuster; Sanjay H. Chotirmall (Mycopathologia, 2020)

Investigation of Siderophore-Promoted and Reductive Dissolution of Dust in Marine Microenvironments Such as Trichodesmium Colonies - Nivi Kessler; Stephan M. Kraemer; Yeala Shaked; Walter D. C. Schenkeveld (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of inorganic nitrate and nitrite consumption on cognitive function and cerebral blood flow: A systematic review and meta-analysis of randomized clinical trials - Tom Clifford; Abrar Babateen; Oliver M. Shannon; Tess Capper; Ammar Ashor; Blossom Stephan; Louise Robinson; John P. O'Hara; John C. Mathers; Emma Stevenson; Mario Siervo (Critical Reviews in Food Science and Nutrition, 2019)

Differential expression of PKCα and -β in the zebrafish retina - Marion F. Haug; Manuela Berger; Matthias Gesemann; Stephan C. F. Neuhauss (Histochemistry and Cell Biology, 2019)

Fate of large-scale vortices in idealized tidal lagoons - Carolanne V. M. Vouriot; Athanasios Angeloudis; Stephan C. Kramer; Matthew D. Piggott (Environmental Fluid Mechanics, 2019)

Overwhelming effects of autumn-time drought during seedling establishment impair recovery potential in sown and semi-natural pastures in Portugal - Marjan Jongen; Alina C. Förster; Stephan Unger (Plant Ecology, 2019)

Cholesterol profile in women with premature menopause after risk reducing salpingo-oophorectomy - Natalia Teixeira; Marian J. Mourits; Jan C. Oosterwijk; Ingrid E. Fakkert; Anthony R. Absalom; Stephan J. L. Bakker; Peter van der Meer; Geertruida H. de Bock (Familial Cancer, 2019)

Climate change opens new frontiers for marine species in the Arctic: Current trends and future invasion risks - Farrah T. Chan; Keara Stanislawczyk; Anna C. Sneekes; Alexander Dvoretsky; Stephan Gollasch; Dan Minchin; Matej David; Anders Jelmert; Jon Albretsen; Sarah A. Bailey (Global Change Biology, 2019)
Climate change and increased anthropogenic activities are expected to elevate the potential of introducing nonindigenous species (NIS) into the Arctic. Yet, the knowledge base needed to identify gaps and priorities for NIS research and management is limited. Here, we reviewed primary introduction events to each ecoregion of the marine Arctic realm to identify temporal and spatial patterns, likely source regions of NIS, and the putative introduction pathways. We included 54 introduction events representing 34 unique NIS. The rate of NIS discovery ranged from zero to four species per year between 1960 and 2015. The Iceland Shelf had the greatest number of introduction events ( n = 14), followed by the Barents Sea ( n = 11), and the Norwegian Sea ( n = 11). Sixteen of the 54 introduction records had no known origins. The majority of those with known source regions were attributed to the Northeast Atlantic and the Northwest Pacific, 19 and 14 records, respectively. Some introduction events were attributed to multiple possible pathways. For these introductions, vessels transferred the greatest number of aquatic NIS (39%) to the Arctic, followed by natural spread (30%) and aquaculture activities (25%). Similar trends were found for introductions attributed to a single pathway. The phyla Arthropoda and Ochrophyta had the highest number of recorded introduction events, with 19 and 12 records, respectively. Recommendations including vector management, horizon scanning, early detection, rapid response, and a pan‐Arctic biodiversity inventory are considered in this paper. Our study provides a comprehensive record of primary introductions of NIS for marine environments in the circumpolar Arctic and identifies knowledge gaps and opportunities for NIS research and management. Ecosystems worldwide will face dramatic changes in the coming decades due to global change. Our findings contribute to the knowledge base needed to address two aspects of global change—invasive species and climate change.

The contributions of local and remote atmospheric moisture fluxes to East Asian precipitation and its variability - Liang Guo; Nicholas P. Klingaman; Marie-Estelle Demory; Pier Luigi Vidale; Andrew G. Turner; Claudia C. Stephan (Climate Dynamics, 2018)

Anti-inflammatory effects of Phaeodactylum tricornutum extracts on human blood mononuclear cells and murine macrophages - Ulrike Neumann; Sandrine Louis; Andrea Gille; Felix Derwenskus; Ulrike Schmid-Staiger; Karlis Briviba; Stephan C. Bischoff (Journal of Applied Phycology, 2018)

Unlocking historical phenotypic data from an ex situ collection to enhance the informed utilization of genetic resources of barley (Hordeum sp.) - Maria Y. González; Norman Philipp; Albert W. Schulthess; Stephan Weise; Yusheng Zhao; Andreas Börner; Markus Oppermann; Andreas Graner; Jochen C. Reif (Theoretical and Applied Genetics, 2018)

Two contrasting laboratory methods improve Silphium integrifolium Michx. germination rate to agronomically acceptable levels - Stephan Reinert; Kennedy L. Money; Greta B. G. Rockstad; Nolan C. Kane; David L. Van Tassel; Brent S. Hulke (Euphytica, 2018)

Application of the Stable Isotope Label Approach in Clinical Development—Supporting Dissolution Specifications for a Commercial Tablet Product with Tafenoquine, a Long Half-life Compound - Navin Goyal; Khadeeja Mohamed; Katie Rolfe; Satty Sahota; Terry Ernest; Stephan Duparc; Maxine Taylor; Linda Casillas; Gavin C. K. W. Koh (The AAPS Journal, 2018)

Genome size of chrysophytes varies with cell size and nutritional mode - Jana L. Olefeld; Stephan Majda; Dirk C. Albach; Sabina Marks; Jens Boenigk (Organisms Diversity & Evolution, 2018)

Selective inhibition of receptor activator of NF-κB ligand (RANKL) in hematopoietic cells improves outcome after experimental myocardial infarction - Svetlana Slavic; Olena Andrukhova; Kristopher Ford; Stephan Handschuh; Nejla Latic; Ursula Reichart; Soleman Sasgary; Claudia Bergow; Lorenz C. Hofbauer; Paul J. Kostenuik; Reinhold G. Erben (Journal of Molecular Medicine, 2018)

EXIOBASE 3: Developing a Time Series of Detailed Environmentally Extended Multi‐Regional Input‐Output Tables - Konstantin Stadler; Richard Wood; Tatyana Bulavskaya; Carl‐Johan Södersten; Moana Simas; Sarah Schmidt; Arkaitz Usubiaga; José Acosta‐Fernández; Jeroen Kuenen; Martin Bruckner; Stefan Giljum; Stephan Lutter; et al. (Journal of Industrial Ecology, 2018)
Summary Environmentally extended multiregional input‐output (EE MRIO) tables have emerged as a key framework to provide a comprehensive description of the global economy and analyze its effects on the environment. Of the available EE MRIO databases, EXIOBASE stands out as a database compatible with the System of Environmental‐Economic Accounting (SEEA) with a high sectorial detail matched with multiple social and environmental satellite accounts. In this paper, we present the latest developments realized with EXIOBASE 3—a time series of EE MRIO tables ranging from 1995 to 2011 for 44 countries (28 EU member plus 16 major economies) and five rest of the world regions. EXIOBASE 3 builds upon the previous versions of EXIOBASE by using rectangular supply‐use tables (SUTs) in a 163 industry by 200 products classification as the main building blocks. In order to capture structural changes, economic developments, as reported by national statistical agencies, were imposed on the available, disaggregated SUTs from EXIOBASE 2. These initial estimates were further refined by incorporating detailed data on energy, agricultural production, resource extraction, and bilateral trade. EXIOBASE 3 inherits the high level of environmental stressor detail from its precursor, with further improvement in the level of detail for resource extraction. To account for the expansion of the European Union (EU), EXIOBASE 3 was developed with the full EU28 country set (including the new member state Croatia). EXIOBASE 3 provides a unique tool for analyzing the dynamics of environmental pressures of economic activities over time.

Towards Adaptive Grids for Atmospheric Boundary-Layer Simulations - J. Antoon van Hooft; Stéphane Popinet; Chiel C. van Heerwaarden; Steven J. A. van der Linden; Stephan R. de Roode; Bas J. H. van de Wiel (Boundary-Layer Meteorology, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

A biological blueprint for the axons of superficial layer pyramidal cells in cat primary visual cortex - Kevan A. C. Martin; Stephan Roth; Elisha S. Rusch (Brain Structure and Function, 2017)

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Synaptic connections formed by patchy projections of pyramidal cells in the superficial layers of cat visual cortex - German Koestinger; Kevan A. C. Martin; Stephan Roth; Elisha S. Rusch (Brain Structure and Function, 2017)

Comparative transcriptomic analysis identifies evolutionarily conserved gene products in the vertebrate renal distal convoluted tubule - Yuya Sugano; Chiara Cianciolo Cosentino; Dominique Loffing-Cueni; Stephan C. F. Neuhauss; Johannes Loffing (Pflügers Archiv - European Journal of Physiology, 2017)

Localization and pneumococcal alteration of junction proteins in the human alveolar–capillary compartment - Andrea Peter; Diana Fatykhova; Olivia Kershaw; Achim D. Gruber; Jens Rueckert; Jens Neudecker; Mario Toennies; Torsten T. Bauer; Paul Schneider; Maria Schimek; Stephan Eggeling; Norbert Suttorp; et al. (Histochemistry and Cell Biology, 2017)

Effects of ocean acidification increase embryonic sensitivity to thermal extremes in Atlantic cod, Gadus morhua - Flemming T. Dahlke; Elettra Leo; Felix C. Mark; Hans‐Otto Pörtner; Ulf Bickmeyer; Stephan Frickenhaus; Daniela Storch (Global Change Biology, 2017)
Thermal tolerance windows serve as a powerful tool for estimating the vulnerability of marine species and their life stages to increasing temperature means and extremes. However, it remains uncertain to which extent additional drivers, such as ocean acidification, modify organismal responses to temperature. This study investigated the effects of CO 2 ‐driven ocean acidification on embryonic thermal sensitivity and performance in Atlantic cod, Gadus morhua , from the Kattegat. Fertilized eggs were exposed to factorial combinations of two P CO 2 conditions (400 μ atm vs. 1100 μ atm) and five temperature treatments (0, 3, 6, 9 and 12 °C), which allow identifying both lower and upper thermal tolerance thresholds. We quantified hatching success, oxygen consumption ( M O 2 ) and mitochondrial functioning of embryos as well as larval morphometrics at hatch and the abundance of acid–base‐relevant ionocytes on the yolk sac epithelium of newly hatched larvae. Hatching success was high under ambient spawning conditions (3–6 °C), but decreased towards both cold and warm temperature extremes. Elevated P CO 2 caused a significant decrease in hatching success, particularly at cold (3 and 0 °C) and warm (12 °C) temperatures. Warming imposed limitations to M O 2 and mitochondrial capacities. Elevated P CO 2 stimulated M O 2 at cold and intermediate temperatures, but exacerbated warming‐induced constraints on M O 2 , indicating a synergistic interaction with temperature. Mitochondrial functioning was not affected by P CO 2 . Increased M O 2 in response to elevated P CO 2 was paralleled by reduced larval size at hatch. Finally, ionocyte abundance decreased with increasing temperature, but did not differ between P CO 2 treatments. Our results demonstrate increased thermal sensitivity of cod embryos under future P CO 2 conditions and suggest that acclimation to elevated P CO 2 requires reallocation of limited resources at the expense of embryonic growth. We conclude that ocean acidification constrains the thermal performance window of embryos, which has important implication for the susceptibility of cod to projected climate change.

Avoiding an uncertain catastrophe: climate change mitigation under risk and wealth heterogeneity - Thomas C. Brown; Stephan Kroll (Climatic Change, 2017)

Semi-quantitative assessments of dextran toxicity on corneal endothelium: conceptual design of a predictive algorithm - Filip Filev; Ceprail Oezcan; Jana Feuerstacke; Stephan J. Linke; Birgit Wulff; Olaf J. C. Hellwinkel (Cell and Tissue Banking, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A test of the migration-modulation hypothesis in a non-passerine Neotropical migrant, the Blue-winged Teal Anas discors - C. Morgan Wilson; Christopher G. Sims; Stephan J. Schoech; Sarah K. Peltier; Zachary L. Robinson (Journal of Ornithology, 2017)

What's your move? Movement as a link between personality and spatial dynamics in animal populations - Orr Spiegel; Stephan T. Leu; C. Michael Bull; Andrew Sih (Ecology Letters, 2017)
Recent studies have established the ecological and evolutionary importance of animal personalities. Individual differences in movement and space‐use, fundamental to many personality traits (e.g. activity, boldness and exploratory behaviour) have been documented across many species and contexts, for instance personality‐dependent dispersal syndromes. Yet, insights from the concurrently developing movement ecology paradigm are rarely considered and recent evidence for other personality‐dependent movements and space‐use lack a general unifying framework. We propose a conceptual framework for personality‐dependent spatial ecology. We link expectations derived from the movement ecology paradigm with behavioural reaction‐norms to offer specific predictions on the interactions between environmental factors, such as resource distribution or landscape structure, and intrinsic behavioural variation. We consider how environmental heterogeneity and individual consistency in movements that carry‐over across spatial scales can lead to personality‐dependent: (1) foraging search performance; (2) habitat preference; (3) home range utilization patterns; (4) social network structure and (5) emergence of assortative population structure with spatial clusters of personalities. We support our conceptual model with spatially explicit simulations of behavioural variation in space‐use, demonstrating the emergence of complex population‐level patterns from differences in simple individual‐level behaviours. Consideration of consistent individual variation in space‐use will facilitate mechanistic understanding of processes that drive social, spatial, ecological and evolutionary dynamics in heterogeneous environments.

Meteorology and oceanography of the Atlantic sector of the Southern Ocean—a review of German achievements from the last decade - Hartmut H. Hellmer; Monika Rhein; Günther Heinemann; Janna Abalichin; Wafa Abouchami; Oliver Baars; Ulrich Cubasch; Klaus Dethloff; Lars Ebner; Eberhard Fahrbach; Martin Frank; Gereon Gollan; et al. (Ocean Dynamics, 2016)

A Mesoscale Model-Based Climatography of Nocturnal Boundary-Layer Characteristics over the Complex Terrain of North-Western Utah - Stefano Serafin; Stephan F. J. De Wekker; Jason C. Knievel (Boundary-Layer Meteorology, 2016)

Rare copy number variants and congenital heart defects in the 22q11.2 deletion syndrome - Elisabeth E. Mlynarski; Michael Xie; Deanne Taylor; Molly B. Sheridan; Tingwei Guo; Silvia E. Racedo; Donna M. McDonald-McGinn; Eva W. C. Chow; Jacob Vorstman; Ann Swillen; Koen Devriendt; Jeroen Breckpot; et al. (Human Genetics, 2016)

Simvastatin induces mitochondrial dysfunction and increased atrogin-1 expression in H9c2 cardiomyocytes and mice in vivo - Annalisa Bonifacio; Peter J. Mullen; Ileana Scurtu Mityko; Luiz C. Navegantes; Jamal Bouitbir; Stephan Krähenbühl (Archives of Toxicology, 2016)

Far-Field Tsunami Impact in the North Atlantic Basin from Large Scale Flank Collapses of the Cumbre Vieja Volcano, La Palma - Babak Tehranirad; Jeffrey C. Harris; Annette R. Grilli; Stephan T. Grilli; Stéphane Abadie; James T. Kirby; Fengyan Shi (Pure and Applied Geophysics, 2015)

Aboveground vertebrate and invertebrate herbivore impact on net N mineralization in subalpine grasslands - Anita C. Risch; Martin Schütz; Martijn L. Vandegehuchte; Wim H. van der Putten; Henk Duyts; Ursina Raschein; Dariusz J. Gwiazdowicz; Matt D. Busse; Deborah S. Page-Dumroese; Stephan Zimmermann (Ecology, 2015)
Aboveground herbivores have strong effects on grassland nitrogen (N) cycling. They can accelerate or slow down soil net N mineralization depending on ecosystem productivity and grazing intensity. Yet, most studies only consider either ungulates or invertebrate herbivores, but not the combined effect of several functionally different vertebrate and invertebrate herbivore species or guilds. We assessed how a diverse herbivore community affects net N mineralization in subalpine grasslands. By using size‐selective fences, we progressively excluded large, medium, and small mammals, as well as invertebrates from two vegetation types, and assessed how the exclosure types (ET) affected net N mineralization. The two vegetation types differed in long‐term management (centuries), forage quality, and grazing history and intensity. To gain a more mechanistic understanding of how herbivores affect net N mineralization, we linked mineralization to soil abiotic (temperature; moisture; NO 3 − , NH 4 + , and total inorganic N concentrations/pools; C, N, P concentrations; pH; bulk density), soil biotic (microbial biomass; abundance of collembolans, mites, and nematodes) and plant (shoot and root biomass; consumption; plant C, N, and fiber content; plant N pool) properties. Net N mineralization differed between ET, but not between vegetation types. Thus, short‐term changes in herbivore community composition and, therefore, in grazing intensity had a stronger effect on net N mineralization than long‐term management and grazing history. We found highest N mineralization values when only invertebrates were present, suggesting that mammals had a negative effect on net N mineralization. Of the variables included in our analyses, only mite abundance and aboveground plant biomass explained variation in net N mineralization among ET. Abundances of both mites and leaf‐sucking invertebrates were positively correlated with aboveground plant biomass, and biomass increased with progressive exclusion. The negative impact of mammals on net N mineralization may be related partially to (1) differences in the amount of plant material (litter) returned to the belowground subsystem, which induced a positive bottom‐up effect on mite abundance, and (2) alterations in the amount and/or distribution of dung, urine, and food waste. Thus, our results clearly show that short‐term alterations of the aboveground herbivore community can strongly impact nutrient cycling within ecosystems independent of long‐term management and grazing history.

Selectivity is species-dependent: Characterization of standard agonists and antagonists at human, rat, and mouse adenosine receptors - Mohamad Wessam Alnouri; Stephan Jepards; Alessandro Casari; Anke C. Schiedel; Sonja Hinz; Christa E. Müller (Purinergic Signalling, 2015)

Microalgae: Fast-Growth Sustainable Green Factories - Eduardo Forján; Francisco Navarro; María Cuaresma; Isabel Vaquero; María C. Ruíz-Domínguez; Živan Gojkovic; María Vázquez; Mayca Márquez; Benito Mogedas; Elizabeth Bermejo; Stephan Girlich; María J. Domínguez; et al. (Critical Reviews in Environmental Science and Technology, 2015)

Neighborhood diversity of large trees shows independent species patterns in a mixed dipterocarp forest in Sri Lanka - Ruwan Punchi-Manage; Thorsten Wiegand; Kerstin Wiegand; Stephan Getzin; Andreas Huth; C. V. Savitri Gunatilleke; I. A. U. Nimal Gunatilleke (Ecology, 2015)
Interactions among neighboring individuals influence plant performance and should create spatial patterns in local community structure. In order to assess the role of large trees in generating spatial patterns in local species richness, we used the individual species–area relationship (ISAR) to evaluate the species richness of trees of different size classes (and dead trees) in circular neighborhoods with varying radius around large trees of different focal species. To reveal signals of species interactions, we compared the ISAR function of the individuals of focal species with that of randomly selected nearby locations. We expected that large trees should strongly affect the community structure of smaller trees in their neighborhood, but that these effects should fade away with increasing size class. Unexpectedly, we found that only few focal species showed signals of species interactions with trees of the different size classes and that this was less likely for less abundant focal species. However, the few and relatively weak departures from independence were consistent with expectations of the effect of competition for space and the dispersal syndrome on spatial patterns. A noisy signal of competition for space found for large trees built up gradually with increasing life stage; it was not yet present for large saplings but detectable for intermediates. Additionally, focal species with animal‐dispersed seeds showed higher species richness in their neighborhood than those with gravity‐ and gyration‐dispersed seeds. Our analysis across the entire ontogeny from recruits to large trees supports the hypothesis that stochastic effects dilute deterministic species interactions in highly diverse communities. Stochastic dilution is a consequence of the stochastic geometry of biodiversity in species‐rich communities where the identities of the nearest neighbors of a given plant are largely unpredictable. While the outcome of local species interactions is governed for each plant by deterministic fitness and niche differences, the large variability of competitors causes also a large variability in the outcomes of interactions and does not allow for strong directed responses at the species level. Collectively, our results highlight the critical effect of the stochastic geometry of biodiversity in structuring local spatial patterns of tropical forest diversity.

Size Exclusion High Performance Liquid Chromatography: Re-Discovery of a Rapid and Versatile Method for Clean-Up and Fractionation in Chemical Ecology - Sergej Sperling; Stephan Kühbandner; Katharina C. Engel; Sandra Steiger; Johannes Stökl; Joachim Ruther (Journal of Chemical Ecology, 2015)

Modeling of SMF tsunami hazard along the upper US East Coast: detailed impact around Ocean City, MD - Stephan T. Grilli; Christopher O’Reilly; Jeffrey C. Harris; Tayebeh Tajalli Bakhsh; Babak Tehranirad; Saeideh Banihashemi; James T. Kirby; Christopher D. P. Baxter; Tamara Eggeling; Gangfeng Ma; Fengyan Shi (Natural Hazards, 2015)

Neuroleptic malignant syndrome and the catatonic dilemma - Stanley N. Caroff; Stephan C. Mann; E. Cabrina Campbell (Psychopharmacology, 2015)

Unrealistic Optimism, Fatalism, and Risk-Taking in New Zealand Farmers’ Descriptions of Quad-Bike Incidents: A Directed Qualitative Content Analysis - Lynne Clay; E. Jean C. Hay-Smith; Gareth J. Treharne; Stephan Milosavljevic (Journal of Agromedicine, 2015)

Erratum to: Characterization of circulating microparticle-associated CD39 family ecto-nucleotidases in human plasma - Z. Gordon Jiang; Yan Wu; Eva Csizmadia; Linda Feldbrügge; Keiichi Enjyoji; John Tigges; Vasilis Toxavidis; Holger Stephan; Christa E. Müller; C. James McKnight; Alan Moss; Simon C. Robson (Purinergic Signalling, 2014)

Characterization of circulating microparticle-associated CD39 family ecto-nucleotidases in human plasma - Z. Gordon Jiang; Yan Wu; Eva Csizmadia; Linda Feldbrügge; Keiichi Enjyoji; John Tigges; Vasilis Toxavidis; Holger Stephan; Christina E. Müller; C. James McKnight; Alan Moss; Simon C. Robson (Purinergic Signalling, 2014)

Whole-genome duplication in teleost fishes and its evolutionary consequences - Stella M. K. Glasauer; Stephan C. F. Neuhauss (Molecular Genetics and Genomics, 2014)

Improved virological and immunological efficacy of resistance-guided switch in antiretroviral therapy: a Frankfurt HIV cohort analysis - T. Wolf; B. Fuß; P. Khaykin; A. Berger; G. Knecht; P. Gute; H. R. Brodt; S. Goepel; M. Bickel; M. Stuermer; C. Stephan (Medical Microbiology and Immunology, 2014)

Teleconnecting Consumption to Environmental Impacts at Multiple Spatial Scales - Klaus Hubacek; Kuishuang Feng; Jan C. Minx; Stephan Pfister; Naijun Zhou (Journal of Industrial Ecology, 2014)

Effect of spatial processes and topography on structuring species assemblages in a Sri Lankan dipterocarp forest - Ruwan Punchi-Manage; Thorsten Wiegand; Kerstin Wiegand; Stephan Getzin; C. V. Savitri Gunatilleke; I. A. U. Nimal Gunatilleke (Ecology, 2014)
Niche and neutral theories emphasize different processes that contribute to the maintenance of species diversity and should leave different spatial structures in species assemblages. In this study we used variation partitioning in combination with distance‐based Moran's eigenvector maps and habitat variables to determine the relative importance of the effects of pure habitat, pure spatial, and spatially structured habitat processes on the spatial distribution of tree species composition and richness in a 25‐ha tropical rain forest of Sinharaja/Sri Lanka. We analyzed the contribution of those components at three spatial scales (10 m, 20 m, and 50 m) for all trees and the three life stages: recruits, juveniles, and adults. At the 10‐m scale, 80% of the variation in species composition remained unexplained for recruits and adults, but only 55% for juveniles. With increasingly broader scales these figures were strongly reduced, mainly by an increasing contribution of the spatially structured habitat component, which explained 4–30%, 20–47%, and 8–35% of variation in species composition for recruits, juveniles, and adults, respectively. The pure spatial component was most important at the 20‐m scale and reached 20%, 32%, and 23% for recruits, juveniles, and adults, respectively. The spatially structured habitat component described variability at broader scales than the pure spatial component. Our results suggest that stochastic processes and spatially structuring processes of community dynamics, such as dispersal limitation and habitat association, contributed jointly to explain species composition and richness at the Sinharaja forest, but their relative importance changed with scale and life stage. Species assembly at the local scale was more strongly impacted by stochasticity, whereas the signal of habitat was stronger at the 50‐m scale where plant‐scale stochasticity is averaged out. Recent research points to an emerging consensus on the relative contribution of stochasticity, habitat, and spatial processes in governing community assembly, but how these components change with life stage, and how this is influenced by sample size, remains to be explored.

Application of 15N–18O double stable isotope tracer technique in an agricultural nonpoint polluted river of the Yangtze Delta Region - X. Q. Liang; Z. Y. Nie; M. M. He; R. Guo; C. Y. Zhu; Y. X. Chen; Küppers Stephan (Environmental Science and Pollution Research, 2013)

Schlummerndes Synthesepotenzial in Enzymen: Wie können wir es wecken? - Stephan C. Hammer; Bettina M. Nestl; Bernhard Hauer (BIOspektrum, 2013)

Dose adjustment in patients with liver cirrhosis: impact on adverse drug reactions and hospitalizations - Carmen C. Franz; Carole Hildbrand; Christa Born; Sabin Egger; Alexandra E. Rätz Bravo; Stephan Krähenbühl (European Journal of Clinical Pharmacology, 2013)

SAHIT Investigators—on the Outcome of Some Subarachnoid Hemorrhage Clinical Trials - R. Loch Macdonald; Blessing Jaja; Michael D. Cusimano; Nima Etminan; Daniel Hanggi; David Hasan; Don Ilodigwe; Hector Lantigua; Peter Le Roux; Benjamin Lo; Ada Louffat-Olivares; Stephan Mayer; et al. (Translational Stroke Research, 2013)

Numerical Simulation of the 2011 Tohoku Tsunami Based on a New Transient FEM Co-seismic Source: Comparison to Far- and Near-Field Observations - Stephan T. Grilli; Jeffrey C. Harris; Tayebeh S. Tajalli Bakhsh; Timothy L. Masterlark; Christodoulos Kyriakopoulos; James T. Kirby; Fengyan Shi (Pure and Applied Geophysics, 2013)

Chloride and organic osmolytes: a hybrid strategy to cope with elevated salinities by the moderately halophilic, chloride‐dependent bacterium Halobacillus halophilus - Stephan H. Saum; Friedhelm Pfeiffer; Peter Palm; Markus Rampp; Stephan C. Schuster; Volker Müller; Dieter Oesterhelt (Environmental Microbiology, 2013)
Summary Salt acclimation in moderately halophilic bacteria is the result of action of a grand interplay orchestrated by signals perceived from the environment. To elucidate the cellular players involved in sensing and responding to changing salinities we have determined the genome sequence of Halobacillus halophilus , a Gram‐positive moderate halophilic bacterium that has a strict requirement for the anion chloride. Halobacillus halophilus synthesizes a multitude of different compatible solutes and switches its osmolyte strategy with the external salinity and growth phase. Based on the emerging genome sequence, the compatible solutes glutamate, glutamine, proline and ectoine have already been experimentally studied. The biosynthetic routes for acetyl ornithine and acetyl lysine are also delineated from the genome sequence. Halobacillus halophilus is nutritionally very versatile and most compatible solutes cannot only be produced but also used as carbon and energy sources. The genome sequence unravelled isogenes for many pathways indicating a fine regulation of metabolism. Halobacillus halophilus is unique in integrating the concept of compatible solutes with the second fundamental principle to cope with salt stress, the accumulation of molar concentrations of salt (Cl ‐ ) in the cytoplasm. Extremely halophilic bacteria/archaea, which exclusively rely on the salt‐in strategy, have a high percentage of acidic proteins compared with non‐halophiles with a low percentage. Halobacillus halophilus has an intermediate position which is consistent with its ability to integrate both principles.

Effects of Sublethal Dose of Fipronil on Neuron Metabolic Activity of Africanized Honeybees - Thaisa Cristina Roat; Stephan M. Carvalho; Roberta C. F. Nocelli; Elaine C. M. Silva-Zacarin; Mario Sérgio Palma; Osmar Malaspina (Archives of Environmental Contamination and Toxicology, 2013)

SH3GL2 is frequently deleted in non-small cell lung cancer and downregulates tumor growth by modulating EGFR signaling - Santanu Dasgupta; Jin Sung Jang; Chunbo Shao; Nitai D. Mukhopadhyay; Upneet K. Sokhi; Swadesh K. Das; Mariana Brait; Conover Talbot; Rex C. Yung; Shahnaz Begum; William H. Westra; Mohammad Obaidul Hoque; et al. (Journal of Molecular Medicine, 2013)

The maternal embryonic leucine zipper kinase (MELK) is upregulated in high-grade prostate cancer - Ruprecht Kuner; Maria Fälth; Nicole Chui Pressinotti; Jan C. Brase; Sabrina Balaguer Puig; Jennifer Metzger; Stephan Gade; Georg Schäfer; Georg Bartsch; Eberhard Steiner; Helmut Klocker; Holger Sültmann (Journal of Molecular Medicine, 2013)

Recommendation for the discrimination of human-related and natural seismicity - T. Dahm; D. Becker; M. Bischoff; S. Cesca; B. Dost; R. Fritschen; S. Hainzl; C. D. Klose; D. Kühn; S. Lasocki; Th. Meier; M. Ohrnberger; et al. (Journal of Seismology, 2013)

Soil organisms shape the competition between grassland plant species - Alexander C. W. Sabais; Nico Eisenhauer; Stephan König; Carsten Renker; François Buscot; Stefan Scheu (Oecologia, 2012)

Individual variation in pup vocalizations and absence of behavioral signs of maternal vocal recognition in Weddell seals ( Leptonychotes weddellii ) - Ilse C. Van Opzeeland; Sofie M. Van Parijs; Stephan Frickenhaus; Cornelia M. Kreiss; Olaf Boebel (Marine Mammal Science, 2012)
Individually stereotyped vocalizations often play an important role in relocation of offspring in gregarious breeders. In phocids, mothers often alternate between foraging at sea and attending their pup. Pup calls are individually distinctive in various phocid species. However, experimental evidence for maternal recognition is rare. In this study, we recorded Weddell seal ( Leptonychotes weddellii ) pup vocalizations at two whelping patches in Atka Bay, Antarctica, and explored individual vocal variation based on eight vocal parameters. Overall, 58% of calls were correctly classified according to individual. For males ( n = 12) and females ( n = 9), respectively, nine and seven individuals were correctly identified based on vocal parameters. To investigate whether mothers respond differently to calls of familiar vs . unfamiliar pups, we conducted playback experiments with 21 mothers. Maternal responses did not differ between playbacks of own, familiar, and unfamiliar pup calls. We suggest that Weddell seal pup calls may need to contain only a critical amount of individually distinct information because mothers and pups use a combination of sensory modalities for identification. However, it cannot be excluded that pup developmental factors and differing environmental factors between colonies affect pup acoustic behavior and the role of acoustic cues in the relocation process.

Potential drug-drug interactions and adverse drug reactions in patients with liver cirrhosis - Carmen C. Franz; Sabin Egger; Christa Born; Alexandra E. Rätz Bravo; Stephan Krähenbühl (European Journal of Clinical Pharmacology, 2012)

Matita, a new retroelement from peanut: characterization and evolutionary context in the light of the Arachis A–B genome divergence - Stephan Nielen; Bruna S. Vidigal; Soraya C. M. Leal-Bertioli; Milind Ratnaparkhe; Andrew H. Paterson; Olivier Garsmeur; Angélique D’Hont; Patricia M. Guimarães; David J. Bertioli (Molecular Genetics and Genomics, 2012)

Complete genome of Candidatus Chloracidobacterium thermophilum, a chlorophyll‐based photoheterotroph belonging to the phylum Acidobacteria - Amaya M. Garcia Costas; Zhenfeng Liu; Lynn P. Tomsho; Stephan C. Schuster; David M. Ward; Donald A. Bryant (Environmental Microbiology, 2012)
Summary Candidatus Chloracidobacterium thermophilum, which naturally inhabits microbial mats of alkaline siliceous hot springs in Yellowstone National Park, is the only known chlorophototroph in the phylum Acidobacteria . The Ca . C . thermophilum genome was composed of two chromosomes (2 683 362 bp and 1 012 010 bp), and both encoded essential genes. The genome included genes to produce chlorosomes, the Fenna‐Matthews‐Olson protein, bacteriochlorophylls a and c as principal pigments, and type‐1, homodimeric reaction centres. Ca . C. thermophilum is an aerobic photoheterotroph that lacks the ability to synthesize several essential nutrients. Key genes of all known carbon fixation pathways were absent, as were genes for assimilatory nitrate and sulfate reduction and vitamin B 12 synthesis. Genes for the synthesis of branched‐chain amino acids (valine, isoleucine and leucine) were also absent, but genes for catabolism of these compounds were present. This observation suggested that Ca . C. thermophilum may synthesize branched‐chain amino acids from an intermediate(s) of the catabolic pathway by reversing these reactions. The genome encoded an aerobic respiratory electron transport chain that included NADH dehydrogenase, alternative complex III and cytochrome oxidase. The chromosomes of the laboratory isolate were compared with assembled, metagenomic scaffolds from the major Ca . C. thermophilum population in hot‐spring mats. The larger chromosomes of the two populations were highly syntenous but significantly divergent (∼13%) in sequence. In contrast, the smaller chromosomes have undergone numerous rearrangements, contained many transposases, and might be less constrained by purifying selection than the large chromosomes. Some transposases were homologous to those of mat community members from other phyla.

Evaluation of non-chemical seed treatment methods for control of Alternaria brassicicola on cabbage seeds - Tahsein Amein; Sandra A. I. Wright; Mariann Wikström; Eckhard Koch; Annegret Schmitt; Dietrich Stephan; Marga Jahn; Federico Tinivella; M. Lodovica Gullino; Gustaf Forsberg; Sigrid Werner; Jan van der Wolf; et al. (Journal of Plant Diseases and Protection, 2011)

Inhibition of Polo-like kinase 1 prevents the growth of metastatic breast cancer cells in the brain - Yongzhen Qian; Emily Hua; Kheem Bisht; Stephan Woditschka; Konstantine W. Skordos; David J. Liewehr; Seth M. Steinberg; Edi Brogi; Muzaffar M. Akram; J. Keith Killian; Daniel C. Edelman; Marbin Pineda; et al. (Clinical & Experimental Metastasis, 2011)

A blueprint of ectoine metabolism from the genome of the industrial producer Halomonas elongata DSM 2581 T - Karin Schwibbert; Alberto Marin‐Sanguino; Irina Bagyan; Gabriele Heidrich; Georg Lentzen; Harald Seitz; Markus Rampp; Stephan C. Schuster; Hans‐Peter Klenk; Friedhelm Pfeiffer; Dieter Oesterhelt; Hans Jörg Kunte (Environmental Microbiology, 2011)
Summary The halophilic γ‐proteobacterium Halomonas elongata DSM 2581 T thrives at high salinity by synthesizing and accumulating the compatible solute ectoine. Ectoine levels are highly regulated according to external salt levels but the overall picture of its metabolism and control is not well understood. Apart from its critical role in cell adaptation to halophilic environments, ectoine can be used as a stabilizer for enzymes and as a cell protectant in skin and health care applications and is thus produced annually on a scale of tons in an industrial process using H. elongata as producer strain. This paper presents the complete genome sequence of H. elongata (4 061 296 bp) and includes experiments and analysis identifying and characterizing the entire ectoine metabolism, including a newly discovered pathway for ectoine degradation and its cyclic connection to ectoine synthesis. The degradation of ectoine (doe) proceeds via hydrolysis of ectoine (DoeA) to Nα‐acetyl‐ l ‐2,4‐diaminobutyric acid, followed by deacetylation to diaminobutyric acid (DoeB). In H. elongata , diaminobutyric acid can either flow off to aspartate or re‐enter the ectoine synthesis pathway, forming a cycle of ectoine synthesis and degradation. Genome comparison revealed that the ectoine degradation pathway exists predominantly in non‐halophilic bacteria unable to synthesize ectoine. Based on the resulting genetic and biochemical data, a metabolic flux model of ectoine metabolism was derived that can be used to understand the way H. elongata survives under varying salt stresses and that provides a basis for a model‐driven improvement of industrial ectoine production.

Impact of CD39 and purinergic signalling on the growth and metastasis of colorectal cancer - Beat M. Künzli; Maria-Isabell Bernlochner; Stephan Rath; Samuel Käser; Eva Csizmadia; Keiichi Enjyoji; Peter Cowan; Anthony d’Apice; Karen Dwyer; Robert Rosenberg; Aurel Perren; Helmut Friess; et al. (Purinergic Signalling, 2011)

Early occurrence of lung adenocarcinoma and breast cancer after radiotherapy of a chest wall sarcoma in a patient with a de novo germline mutation in TP53 - Alessandra Ferrarini; Agnes Auteri-Kaczmarek; Alessia Pica; Nemya Boesch; Karl Heinimann; Stephan C. Schäfer; Sara Vesnaver-Megalo; Viviane Cina; Jacques S. Beckmann; Christian Monnerat (Familial Cancer, 2011)

Expression of mRNA Isoforms of Latent Transforming Growth Factor-β Binding Protein-1 in Coronary Atherosclerosis and Human Tissues - Rahmi Öklü; Robin Hesketh; Stephan Wicky; James C. Metcalfe (Biochemical Genetics, 2011)

The influence of refuge sharing on social behaviour in the lizard Tiliqua rugosa - Stephan T. Leu; Peter M. Kappeler; C. Michael Bull (Behavioral Ecology and Sociobiology, 2011)

Transcranial direct current stimulation affects visual perception measured by threshold perimetry - Antje Kraft; Jasper Roehmel; Manuel C. Olma; Sein Schmidt; Kerstin Irlbacher; Stephan A. Brandt (Experimental Brain Research, 2010)

Human immunodeficiency virus type-1 group M quasispecies evolution: diversity and divergence in patients co-infected with active tuberculosis - T. Biru; T. Lennemann; M. Stürmer; C. Stephan; G. Nisius; J. Cinatl; S. Staszewski; L. G. Gürtler (Medical Microbiology and Immunology, 2010)

Refuge sharing network predicts ectoparasite load in a lizard - Stephan T. Leu; Peter M. Kappeler; C. Michael Bull (Behavioral Ecology and Sociobiology, 2010)

Organocopper complexes during roxarsone degradation in wastewater lagoons - Syam S. Andra; Konstantinos C. Makris; Shahida Quazi; Dibyendu Sarkar; Rupali Datta; Stephan B. H. Bach (Environmental Science and Pollution Research, 2010)

Co-culture of primary rat hepatocytes with rat liver epithelial cells enhances interleukin-6-induced acute-phase protein response - Stephan J. A. C. Peters; Tamara Vanhaecke; Peggy Papeleu; Vera Rogiers; Henk P. Haagsman; Klaske van Norren (Cell and Tissue Research, 2010)

Dew Formation, Eddy-Correlation Latent Heat Fluxes, and the Surface Energy Imbalance at Cabauw During Stable Conditions - Stephan R. de Roode; Fred C. Bosveld; Petra S. Kroon (Boundary-Layer Meteorology, 2010)

Evaluation of non-chemical seed treatment methods for the control of Alternaria dauci and A. radicina on carrot seeds - Eckhard Koch; Annegret Schmitt; Dietrich Stephan; Carola Kromphardt; Marga Jahn; Hermann-Josef Krauthausen; Gustaf Forsberg; Sigrid Werner; Tahsein Amein; Sandra A. I. Wright; Federico Tinivella; Maria L. Gullino; et al. (European Journal of Plant Pathology, 2010)

Synthesis of phytochelatins in vetiver grass upon lead exposure in the presence of phosphorus - Syam S. Andra; Rupali Datta; Dibyendu Sarkar; Konstantinos C. Makris; Conor P. Mullens; Shivendra V. Sahi; Stephan B. H. Bach (Plant and Soil, 2010)

Insights into the molecular basis of the microaerophily of three Campylobacterales: a comparative study - Nadeem O. Kaakoush; Claudia Baar; Joanna MacKichan; Peer Schmidt; Edward M. Fox; Stephan C. Schuster; George L. Mendz (Antonie van Leeuwenhoek, 2009)

Evaluation of non-chemical seed treatment methods for the control of Phoma valerianellae on lamb’s lettuce seeds - A. Schmitt; E. Koch; D. Stephan; C. Kromphardt; M. Jahn; H. -J. Krauthausen; G. Forsberg; S. Werner; T. Amein; S. A. I. Wright; F. Tinivella; J. van der Wolf; et al. (Journal of Plant Diseases and Protection, 2009)

Heterogeneous distribution of phosphorus in olivine from otherwise well-equilibrated spinel peridotite xenoliths and its implications for the mantle geochemistry of lithium - Guilherme Mallmann; Hugh St. C. O’Neill; Stephan Klemme (Contributions to Mineralogy and Petrology, 2009)

Physiological and pathophysiological functions of intestinal mast cells - Stephan C. Bischoff (Seminars in Immunopathology, 2009)

Acceptor-photobleaching FRET analysis of core kinetochore and NAC proteins in living human cells - D. Hellwig; C. Hoischen; T. Ulbricht; Stephan Diekmann (European Biophysics Journal, 2009)

Chemical Composition of Cloud Water in the Puerto Rican Tropical Trade Wind Cumuli - Adriana Gioda; Olga L. Mayol-Bracero; Flavia Morales-García; Jeff Collett; Stefano Decesari; Lorenza Emblico; Maria C. Facchini; Ricardo J. Morales-De Jesús; Stephan Mertes; Stephan Borrmann; Saskia Walter; Johannes Schneider (Water, Air, & Soil Pollution, 2009)

Odour-based species recognition in two sympatric species of sac-winged bats (Saccopteryx bilineata, S. leptura): combining chemical analyses, behavioural observations and odour preference tests - Barbara A. Caspers; Frank C. Schroeder; Stephan Franke; W. Jürgen Streich; Christian C. Voigt (Behavioral Ecology and Sociobiology, 2009)

Control of seed-borne pathogens on legumes by microbial and other alternative seed treatments - Federico Tinivella; Lucia M. Hirata; Mikael A. Celan; Sandra A. I. Wright; Tahsein Amein; Annegret Schmitt; Eckhard Koch; Jan M. van der Wolf; Steven P. C. Groot; Dietrich Stephan; Angelo Garibaldi; Maria Lodovica Gullino (European Journal of Plant Pathology, 2009)

Memory and psychostimulants: modulation of Pavlovian fear conditioning by amphetamine in C57BL/6 mice - Suzanne C. Wood; Stephan G. Anagnostaras (Psychopharmacology, 2009)

A new clade of hepatitis B virus subgenotype F1 from Peru with unusual properties - Markus von Meltzer; Silvia Vásquez; Jianguang Sun; Ulrike C. Wendt; Anja May; Wolfram H. Gerlich; Monika Radtke; Stephan Schaefer (Virus Genes, 2008)

A bacterial ice-binding protein from the Vostok ice core - James A. Raymond; Brent C. Christner; Stephan C. Schuster (Extremophiles, 2008)

Molecular characterization ofPseudomonas syringae pv.tomato isolates from Tanzania - K. C. Shenge; D. Stephan; R. B. Mabagala; C. N. Mortensen; K. Wydra (Phytoparasitica, 2008)

Signal transduction underlying the control of urinary bladder smooth muscle tone by muscarinic receptors and β-adrenoceptors - Elfaridah P. Frazier; Stephan L. M. Peters; Alan S. Braverman; Michael R. Ruggieri; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Strategies of a parasite of the ant–Acacia mutualism - Lars W. Clement; Stephan C. W. Köppen; Willi A. Brand; Martin Heil (Behavioral Ecology and Sociobiology, 2008)

Chelerythrine treatment influences the balance of pro- and anti-apoptotic signaling pathways in the remote myocardium after infarction - Gregor Simonis; Stephan Wiedemann; Kerstin Schwarz; Torsten Christ; Daniel G. Sedding; Xinjian Yu; Rainer Marquetant; Ruediger C. Braun-Dullaeus; Ursula Ravens; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Direct Fluorescence Monitoring of Coal Organic Matter Released in Seawater - C. Jaffrennou; L. Stephan; P. Giamarchi; J. Y. Cabon; L. Burel-Deschamps; F. Bautin (Journal of Fluorescence, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Formation of giant spicules in the deep-sea hexactinellid Monorhaphis chuni (Schulze 1904): electron-microscopic and biochemical studies - Werner E. G. Müller; Carsten Eckert; Klaus Kropf; Xiaohong Wang; Ute Schloßmacher; Christopf Seckert; Stephan E. Wolf; Wolfgang Tremel; Heinz C. Schröder (Cell and Tissue Research, 2007)

Validation of a rapid, non-radioactive method to quantify internalisation of G-protein coupled receptors - Maikel Jongsma; Urszula M. Florczyk; Mariëlle C. Hendriks-Balk; Martin C. Michel; Stephan L. M. Peters; Astrid E. Alewijnse (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Mapping diabetes QTL in an intercross derived from a congenic strain of the Brown Norway and Goto-Kakizaki rats - Stephan C. Collins; Robert H. Wallis; Steven P. Wilder; Karin J. Wallace; Karène Argoud; Pamela J. Kaisaki; Marie-Thérèse Bihoreau; Dominique Gauguier (Mammalian Genome, 2006)

Archean diamonds from Wawa (Canada): samples from deep cratonic roots predating cratonization of the Superior Province - Thomas Stachel; Anetta Banas; Karlis Muehlenbachs; Stephan Kurszlaukis; Edward C. Walker (Contributions to Mineralogy and Petrology, 2006)

The impact of climate change on lakes in the Netherlands: a review - Wolf M. Mooij; Stephan Hülsmann; Lisette N. De Senerpont Domis; Bart A. Nolet; Paul L. E. Bodelier; Paul C. M. Boers; L. Miguel Dionisio Pires; Herman J. Gons; Bas W. Ibelings; Ruurd Noordhuis; Rob Portielje; Kirsten Wolfstein; et al. (Aquatic Ecology, 2005)

Novel genes for nitrite reductase and Amo‐related proteins indicate a role of uncultivated mesophilic crenarchaeota in nitrogen cycling - Alexander H. Treusch; Sven Leininger; Arnulf Kletzin; Stephan C. Schuster; Hans‐Peter Klenk; Christa Schleper (Environmental Microbiology, 2005)
Summary Mesophilic crenarchaeota are frequently found in terrestrial and marine habitats worldwide, but despite their considerable abundance the physiology of these as yet uncultivated archaea has remained unknown. From a 1.2 Gb large‐insert environmental fosmid library of a calcareous grassland soil, a 43 kb genomic fragment was isolated with a ribosomal RNA that shows its affiliation to group 1.1b of crenarchaeota repeatedly found in soils. The insert encoded a homologue of a copper‐containing nitrite reductase with an unusual C‐terminus that encoded a potential amicyanin‐like electron transfer domain as well as two proteins related to subunits of ammonia monooxygenases or particulate methane monooxygenases (AmoAB/PmoAB) respectively. Expression of nirK and the amo A‐like gene was shown by reverse transcription polymerase chain reaction (PCR) analyses in soil samples, the latter being found at higher levels when the soil was incubated with ammonia (measured by quantitative PCR). Further variants of both genes were amplified from soil samples and were found in the environmental database from the Sargasso Sea plankton. Taken together, our findings suggest that mesophilic terrestrial and marine crenarchaeota might be capable of ammonia oxidation under aerobic and potentially also under anaerobic conditions.

Survey of potential sapstain fungi on Pinus radiata in New Zealand - Joanne M. Thwaites; Roberta L. Farrell; Shona M. Duncan; Stephan D. Reay; Robert A. Blanchette; Esther Hadar; Yitzhak Hadar; Thomas C. Harrington; Douglas McNew (New Zealand Journal of Botany, 2005)
A nationwide survey of New Zealand sapstain fungi on Pinus radiata was undertaken between 1996 and 1998 with collections of 1958 samples of material from 869 sites in the North and South Islands. Material was collected from mills, ports, forest plantations of native, exotic, or P. radiata , nurseries, farms, and urban areas. Material collected included branches, twigs, needles or leaves, cones, logs, wood chips, timber, and veneer. From these collections, 2154 potential sapstain fungi, representing 14 known species plus a number of unidentified species, were isolated. The predominant sapstain fungi isolated were Sphaeropsis sapinea, Ophiostoma ips, O. floccosum, O. piliferum, Leptographium procerum , and O. querci. S. sapinea was isolated from all material sampled including collections from the forest floor (including branches, twigs, needles, leaves, cones, and logs) as well as from logs and timber. In contrast Ophiostoma species were mainly found on logs, timber, and wood chips.

Characterization of large‐insert DNA libraries from soil for environmental genomic studies of Archaea - Alexander H. Treusch; Arnulf Kletzin; Guenter Raddatz; Torsten Ochsenreiter; Achim Quaiser; Guido Meurer; Stephan C. Schuster; Christa Schleper (Environmental Microbiology, 2004)
Summary Complex genomic libraries are increasingly being used to retrieve complete genes, operons or large genomic fragments directly from environmental samples, without the need to cultivate the respective microorganisms. We report on the construction of three large‐insert fosmid libraries in total covering 3 Gbp of community DNA from two different soil samples, a sandy ecosystem and a mixed forest soil. In a fosmid end sequencing approach including 5376 sequence tags of ≈ 700 bp length, we show that mostly bacterial and, to a much lesser extent, archaeal and eukaryotic genome fragments (≈ 1% each) have been captured in our libraries. The diversity of putative protein‐encoding genes, as reflected by their distribution into different COG clusters, was comparable to that encoded in complete genomes of cultivated microorganisms. A huge variety of genomic fragments has been captured in our libraries, as seen by comparison with sequences in the public databases and by the large variation in G+C contents. We dissect differences between the libraries, which relate to the different ecosystems analysed and to biases introduced by different DNA preparations. Furthermore, a range of taxonomic marker genes (other than 16S rRNA) has been identified that allows the assignment of genome fragments to specific lineages. The complete sequences of two genome fragments identified as being affiliated with Archaea, based on a gene encoding a CDC48 homologue and a thermosome subunit, respectively, are presented and discussed. We thereby extend the genomic information of uncultivated crenarchaeota from soil and offer hints to specific metabolic traits present in this group.

Post-Translational Modifications of Proteins: Implications for Aging, Antigen Recognition, and Autoimmunity - Paul A. C. Cloos; Stephan Christgau (Biogerontology, 2004)

Behavioural structuring of relatedness in the spotted hyena ( Crocuta crocuta ) suggests direct fitness benefits of clan‐level cooperation - Russell C. Van Horn; Anne L. Engh; Kim T. Scribner; Stephan M. Funk; Kay E. Holekamp (Molecular Ecology, 2004)
Spotted hyenas ( Crocuta crocuta ) are gregarious carnivores that live in multigenerational social groups, called clans, containing one to several matrilines. Members of multiple matrilines within a clan cooperate during dangerous interactions with inter‐ and intraspecific competitors. The evolution of cooperation may be influenced by relatedness between individuals, which in turn is influenced by reproductive skew and mate choice, dispersal and territorial behaviours. Behavioural data exist for spotted hyenas, but corresponding data on patterns of relatedness are unavailable; this lack of data makes it difficult to assess the relative importance of selection pressures favouring cooperative behaviour within and among groups. Therefore we conducted a longitudinal analysis of relatedness within a single large clan of spotted hyenas, as well as a cross‐sectional analysis of relatedness among hyenas from multiple clans. Within a clan, patterns of relatedness reflected known pedigree relationships, and relatedness was higher within than among matrilines, even across generations. Although mean within‐matriline relatedness varied among matrilines, it did not decline with matriline rank. On average, clan members were not related closely, due to high levels of male‐mediated gene flow among clans, and relatedness declined very slightly across clan borders. Low mean relatedness within clans suggests that spotted hyenas cooperate with unrelated clan‐mates against close paternal kin in other clans. Our data also suggest that spotted hyenas must derive large net direct fitness benefits from group living and cooperation.

Periglacial trimlines and nunataks of the Last Glacial Maximum: the Gap of Dunloe, southwest Ireland - Alaric C. Rae; Stephan Harrison; Timothy Mighall; Alastair G. Dawson (Journal of Quaternary Science, 2004)
During the last main phase of glaciation (26–13 ka) an ice‐cap developed in southwest Ireland and ice, from a dispersal centre in the vicinity of Kenmare, flowed north through the Gap of Dunloe in the Macgillycuddy's Reeks. On surrounding hillsides a weathering limit separates ice‐moulded bedrock, on low ground, from frost‐weathered terrain above. Assessment of bedrock dilation joint characteristics, Schmidt hammer R ‐value data and clay‐sized mineral contents of basal soil samples, demonstrate significant contrasts in the degree of weathering above and below this limit. The weathering limit declines in altitude along former ice flow‐lines and is confluent with morainic deposits on the eastern side of the Gap. This supports the assertion that the high‐level weathering limit is a periglacial trimline that marks the former maximum upper limit of the body of ice which occupied the Gap of Dunloe during the Last Glacial Maximum (LGM). Reconstruction of the former ice‐surface profile from periglacial trimline limits on the eastern side of the Gap yields a mean estimate for basal shear stress of 106.5 kPa. This value suggests that the ice mass which occupied the Gap of Dunloe at the LGM was warm based and flowed on a bedrock substrate. Copyright © 2004 John Wiley & Sons, Ltd.

Gene arrays and temporal patterns of drug response: corticosteroid effects on rat liver - Richard R. Almon; Debra C. DuBois; Keri E. Pearson; Dietrich A Stephan; William J. Jusko (Functional & Integrative Genomics, 2003)

cAMP-independent relaxation of smooth muscle cells via G s -coupled receptors - Stephan L. M. Peters; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

High-frequency transcranial magnetic stimulation of the supplementary motor area reduces bimanual coupling during anti-phase but not in-phase movements - Hartwig R. Siebner; Maarten Steyvers; Seiji Etoh; Stephan P. Swinnen; Dieter Sauner; Oron Levin; John C. Rothwell (Experimental Brain Research, 2003)

Discovery of an extended bundle sheath in Ricinus communis L. and its role as a temporal storage compartment for the iron chelator nicotianamine - T. Rutten; C. Krger; M. Melzer; U. W. Stephan; R. Hell (Planta, 2003)

Marker-assisted congenic screening ( MACS ): A database tool for the efficient production and characterization of congenic lines - Stephan C. Collins; Robert H. Wallis; Karin Wallace; Marie Thrse Bihoreau; Dominique Gauguier (Mammalian Genome, 2003)

Markers of inflammation and myofibrillar proteins following eccentric exercise in humans - Donna L. MacIntyre; Stephan Sorichter; Johannes Mair; Donald C. McKenzie; Aloys Berg (European Journal of Applied Physiology, 2001)

Suppression of apoptosis and induction of DNA synthesis in vitro by the phthalate plasticizers monoethylhexylphthalate (MEHP) and diisononylphthalate (DINP): a comparison of rat and human hepatocytes in vitro - Susan C. Hasmall; Neil H. James; Neil Macdonald; Douglas West; Stephan Chevalier; Sabina C. Cosulich; Ruth A. Roberts (Archives of Toxicology, 1999)

Granulocyte-colony stimulating factor decreases glycosaminoglycan concentration and increases nitric oxide production in rat articular cartilage - S. Stephan; W. M. Purcell , C. L. Chander (Inflammation Research, 1999)

The ability of nicotine to induce glycosaminoglycan release in porcine nasal cartilage explant cultures - R. Misra; S. Stephan; C. L. Chander (Inflammation Research, 1999)

Effects of a Population Bottleneck on Whooping Crane Mitochondrial DNA Variation - Travis C. Glenn; Wolfgang Stephan; Michael J. Braun (Conservation Biology, 1999)
The Whooping Crane ( Grus americana ) is an endangered bird that suffered a severe population bottleneck; only 14 adults survived in 1938. We assessed the genetic effect of this human‐caused bottleneck by sequencing 314 base pairs ( bp) of the mitochondrial DNA control region from cranes that lived before, during, and after this bottleneck. The maximum length of DNA amplifiable from museum specimens was negatively correlated with age, and only 10 of 153 specimens yielded the entire 314 bp sequence. Six haplotypes were present among the prebottleneck individuals sequenced, and only one of these persists in the modern population. The most common modern haplotype was in low frequency in the prebottleneck population, which demonstrates the powerful effect of genetic drift in changing allele frequencies in very small populations. By combining all available data, we show that no more than one‐third of the prebottleneck haplotypes survived the human‐caused population bottleneck. High levels of variation of substitution rates among nucleotide sites prevented us from estimating the prebottleneck population size. Our data will be incorporated into the captive breeding program to allow better management decisions regarding the preservation of current genetic diversity. These data offer the first glimpse into the genetic toll this species has paid for human activities.

Sea-breeze Front Variations in Space and Time - K. Stephan; H. Kraus; C. M. Ewenz; J. M. Hacker (Meteorology and Atmospheric Physics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

HLA-DRB1 * 03 , but not the TNFA -308 promoter gene polymorphism, confers protection against fistulising Crohn's disease - G. Bouma; Alexander C. Poen; M. Asunción García-González; Geziena M. T. Schreuder; Richelle J. F. Felt-Bersma; Stephan G. M. Meuwissen; A. S. Peña (Immunogenetics, 1998)

The reaction MgCr 2 O 4 + SiO 2 = Cr 2 O 3 + MgSiO 3 and the free energy of formation of magnesiochromite (MgCr 2 O 4 ) - Stephan Klemme; Hugh S. C. O'Neill (Contributions to Mineralogy and Petrology, 1997)

Analyzing Outcrop-Scale Fracture Features to Supplement Investigations of Bedrock Aquifers - Stephan B. Mabee; Kenneth C. Hardcastle (Hydrogeology Journal, 1997)

Delayed breeding in the cooperatively breeding Florida scrub-jay ( Aphelocoma coerulescens ): inhibition or the absence of stimulation? - Stephan J. Schoech; Ronald L. Mumme; John C. Wingfield (Behavioral Ecology and Sociobiology, 1996)